Glass ceramics with specific thermal expansion properties

A LAS glass ceramic with optimized SiO2, Li2O, and controlled oxides achieves zero thermal expansion and reduced hysteresis, addressing accuracy issues in precision components and enabling large-scale production without toxic refining agents.

CN119191715APending Publication Date: 2024-12-27SCHOTT AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411393069.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-12-22
Filing Date
2022-03-15
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing glass ceramics, particularly LAS glass ceramics, exhibit thermal hysteresis and isothermal length changes, which affect the accuracy of precision components used in applications near room temperature, and the use of toxic refining agents like arsenic oxide complicates large-scale production.

Method used

A LAS glass ceramic composition with a specific range of SiO2, Li2O, and controlled amounts of MgO, ZnO, and other oxides, along with minimal As2O3, is developed to achieve zero thermal expansion and reduced hysteresis in the 10°C to 35°C range, using environmentally friendly refining methods.

Benefits of technology

The new glass ceramic achieves zero thermal expansion and minimal hysteresis, improving the accuracy of precision components and enabling large-scale production without toxic refining agents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191715A_ABST
    Figure CN119191715A_ABST
Patent Text Reader

Abstract

The invention relates to glass ceramics having an improved thermal expansion behavior and to the use thereof in precision parts.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of patent application 202210266155.4 filed on March 15, 2022, with the invention name “Glass ceramics with specific thermal expansion properties”. Technical Field

[0002] The invention relates to a glass ceramic having a specific thermal expansion behavior and at the same time good melting properties, more environmentally friendly fining, shaping and ceramization, and to the use of the glass ceramic according to the invention in precision components. Background Art

[0003] Materials and precision components with low thermal expansion or low CTE (Coefficient of Thermal Expansion) are known in the art.

[0004] Ceramics, titanium-doped quartz glass and glass ceramics are known as precision component materials with low thermal expansion in the temperature range around room temperature. Glass ceramics with low thermal expansion are especially lithium aluminum silicate glass ceramics (LAS glass ceramics), which are described, for example, in US 4,851,372, US 5,591,682, EP 587979A, US 7,226,881, US 7,645,714, DE 102004008824 A, DE 102018111144 A. Other materials for precision components are cordierite ceramics or cordierite glass ceramics.

[0005] Such materials are often used for precision components that must meet particularly stringent requirements regarding their properties (e.g. mechanical, physical, optical properties). They are used in particular in terrestrial and space-based astronomy and Earth observation, LCD lithography, microlithography and EUV lithography, metrology, spectroscopy and measurement technology. In this case, it is required that the components have a particularly low thermal expansion, depending on the specific application.

[0006] Usually, the thermal expansion of a material is determined by a static method, in which the length of the test piece is determined at the beginning and end of a certain temperature interval and the average expansion coefficient α or CTE (coefficient of thermal expansion) is calculated from the length difference. The CTE is then designated as the average value for the temperature interval, for example CTE (0; 50) or α (0; 50) for a temperature interval of 0°C to 50°C.

[0007] In order to meet the growing demand, materials have been developed with a CTE that is better adapted to the application field of the components formed by the material. For example, the average CTE can be optimized not only for the standard temperature interval CTE (0; 50), but also for example for a temperature interval near the actual application temperature, such as the interval from 19°C to 25°C, i.e. CTE (19; 25) for certain lithography applications. In addition to determining the average CTE, the thermal expansion of the test piece can also be determined in a very small temperature interval and thus represented by a CTE-T curve. Preferably, such a CTE-T curve can have a zero crossing at one or more temperatures, preferably at or close to the expected application temperature. At the zero crossing of the CTE-T curve, the relative length change with temperature is particularly small. For some glass-ceramics, the zero crossing of this CTE-T curve can be transferred to the application temperature of the component by appropriate temperature treatment. In addition to the absolute CTE value, the slope of the CTE-T curve near the application temperature should also be as small as possible so that the length change of the component is as small as possible when a small temperature change occurs. For these special zero-expansion glass-ceramics, the above-mentioned optimization of CTE or thermal expansion is achieved by varying the ceramizing conditions while keeping the composition constant.

[0008] In the case of known precision components and materials, in particular in the case of glass ceramics such as LAS glass ceramics, one adverse effect is the so-called "thermal hysteresis", hereinafter referred to as "hysteresis". Hysteresis refers to the difference between the change in length of a test piece when it is heated at a constant heating rate and the change in length of the test piece when it is subsequently cooled at a constant cooling rate, even if the cooling rate and the heating rate are the same in magnitude. If the change in length is displayed graphically as a function of the temperature used for heating or cooling, a classic hysteresis loop results. The shape of the hysteresis loop also depends on the rate of temperature change. The faster the temperature change, the more pronounced the hysteresis effect. The hysteresis effect clearly shows that the thermal expansion of LAS glass ceramics depends on temperature and time, i.e., for example, on the rate of temperature change, which has also been described in the specialist literature elsewhere, for example O. Lindig and W. Pannhorst, "Glass Ceramics: Thermal Insulation and Thermal Properties of Glass Ceramics". Thermal expansion and length stability as a function of temperature and time”, Applied Optics, Vol. 24, No. 20, October 1985; R. Haug et al., “Glass-ceramics Length variation in the temperature range -60°C to +100°C”, Applied Optics, Vol. 28, No. 19, October 1989; R. Jedamzik ​​et al., “Glass-ceramics The thermal expansion behavior at any temperature curve 7739, 2010; D.B. Hall, “Dimensional stability of several low expansion glass-ceramics over time and temperature,” Applied Optics, Vol. 35, No. 10, April 1996.

[0009] Since the length change of glass ceramics exhibiting thermal hysteresis lags or leads the temperature change, the material or precision components made of it exhibit a disruptive isothermal length change, i.e. after a temperature change, the length change of the material still occurs when the temperature has been kept constant (so-called "isothermal holding") and until a steady state is reached. The same effect reappears when the material is subsequently heated and cooled again.

[0010] For the LAS glass-ceramics known to date, it has not been possible to eliminate the thermal hysteresis effect without affecting the other properties, despite varying the ceramizing conditions while keeping the composition constant.

[0011] Regarding the properties of materials, especially glass ceramics, for precision components, it is usually relevant to have a temperature range of 0°C to 50°C, especially 10°C to 35°C or 19°C to 25°C, wherein a temperature of 22°C is usually referred to as room temperature. Since many applications of precision components occur in a temperature range of greater than 0°C to room temperature, materials with thermal hysteresis effects and isothermal length changes are disadvantageous, since optical interference may occur in optical components such as lithography mirrors and astronomical or space-based mirrors. This may lead to inaccurate measurements of other precision components made of glass ceramics used in measurement technology (e.g. precision measuring rods, reference plates in interferometers).

[0012] Some well-known materials such as ceramics, titanium-doped quartz glass and some glass-ceramics have an excellent accuracy of 0±0.1x10 -6 / K (corresponding to 0±0.1 ppm / K) with an average coefficient of thermal expansion CTE (0; 50). Materials with such a low average CTE in the temperature range mentioned are referred to as zero expansion materials within the meaning of the present invention. However, glass ceramics, in particular LAS glass ceramics, whose average CTE is optimized in this way, usually have thermal hysteresis in a temperature range of 10°C to 35°C. This means that these materials will experience disturbing hysteresis effects, especially in applications at room temperature (i.e. 22°C), which will impair the accuracy of precision parts made of such materials. Therefore, a glass ceramic material has been developed (see US 4,851,372), which has no obvious hysteresis at room temperature, but the effect is not eliminated, but only transferred to lower temperatures, so that this glass ceramic shows obvious hysteresis at temperatures of 10°C and below, which may still be disturbing. In order to characterize the thermal hysteresis properties of a material in a specific temperature range, the thermal behavior of the material is therefore observed at different temperature points within this range within the scope of the present invention. There are even glass-ceramics which do not show any significant hysteresis at 22°C and 5°C, but these glass-ceramics have an average CTE (0;50) > 0 ± 0.1 ppm / K and are therefore not zero-expansion glass-ceramics in the sense defined above.

[0013] Another requirement for glass-ceramic materials is good solubility of the glass components and easy melting and homogenization of the initial glass melt in large-scale production facilities so that after the glass is ceramicized, the high requirements placed on the glass-ceramic in terms of CTE uniformity, internal quality - especially the small number of inclusions (especially bubbles), low streak level - and polishability are met.

[0014] The internal quality of glass ceramics, especially features such as bubbles and streaks, is influenced by how well the glass melt is refined. Refining is the removal of gas bubbles from the glass melt. The molten mixture needs to be thoroughly mixed and degassed to avoid foreign gases and bubbles as much as possible. For this purpose, compounds, so-called chemical fining agents, are usually added to the melt, which decompose and release gases there or evaporate at higher temperatures. A particularly effective fining agent for LAS glass ceramics is arsenic oxide (As 2 O 3 ), which acts as a redox clarifier to release clarified gas O 2 This fining agent is particularly effective because, as disclosed in DE 10 2010 002 188 A1, the release of fining gas has two maxima at temperatures (approximately 1250° C. and approximately 1600° C.) which lie within the temperature range of melting and fining of the glass components. 2 O 3 It is highly toxic and classified as a carcinogen.

[0015] In the field of zero expansion LAS glass ceramics, relative to As2 O 3 , efforts have been made to use other chemical refining agents (e.g. US8043985 B2, DE 102010002188 A1). However, a general problem with the use of refining agents is that the added refining agents, on the one hand, release refining gases by decomposition or due to their volatility, but on the other hand, also remain at least partially as components in the glass phase and / or the crystal phase and thus also determine the properties of the subsequent glass ceramics. For example, DE 19939771 A also discloses refining a glass melt at very high temperatures in the range of 1700° C. to 2400° C. by adding different refining agents.

[0016] Purpose of the Invention

[0017] The object of the present invention is therefore to provide an environmentally friendly refined glass ceramic with improved expansion behavior. Another object is to provide an environmentally friendly refined, large-scale producible glass ceramic, in particular with zero expansion and reduced thermal hysteresis in the temperature range of 10° C. to 35° C., and precision components made of this material.

[0018] The above objects are achieved by the subject matter of the patent claims. The invention has different aspects:

[0019] According to one aspect of the present invention, a LAS glass ceramic is provided, which has a maximum temperature of 0±0.1x 10 -6 The invention relates to a composite material having an average thermal expansion coefficient of 0.1 ppm and a thermal hysteresis of at least 0.1 ppm in the temperature range of 10-35 °C, and comprises the following components (in Mol % based on oxides): SiO 2 60–71

[0020] Li 2 O 7–9.4

[0021] MgO+ZnO 0–<0.6

[0022] Choose from P 2 O 5 , R 2 At least one component of the group consisting of O and RO, wherein R 2 O can be Na 2 O and / or K 2 O and / or Cs 2 O and / or Rb 2 O, and RO can be CaO and / or BaO and / or SrO, the content of the nucleating agent is 1.5 to 6 Mol%, wherein the nucleating agent is selected from TiO 2 、ZrO 2 、 2 O5 , Nb 2 O 5 SnO 2 、MoO 3 , WO 3 , HfO 2 At least one component of the group consisting of

[0023] Among them, LAS glass ceramics contain up to 0.05Mol% As 2 O 3 .

[0024] According to a further aspect, the invention relates to the use of the glass ceramic according to the invention as a substrate for a precision component.

[0025] According to a further aspect, the invention relates to the use of the LAS glass-ceramic according to the invention in precision components, in particular for use in metrology, spectroscopy, measuring technology, lithography, astronomy or Earth observation from space, for example as mirrors or mirror carriers for segmented or integral astronomical telescopes, or also as reduced-weight or ultra-light mirror substrates, for example for space-based telescopes, or as high-precision structural components for distance measurement, for example in optics in space or for Earth observation, as precision components, for example standards for precise measuring technology, precision measuring rods, reference plates in interferometers, as mechanical precision components, for example for ring laser gyroscopes, helical springs for watchmaking, for example as mirrors and prisms in LCD lithography, for example as mask holders, wafer stages, reference plates, reference frames and grid plates in microlithography and EUV (extreme ultraviolet) microlithography in which reflective optics are used, and as mirrors and / or photomask substrates or photomask blanks in EUV microlithography.

[0026] According to a further aspect, the invention relates to a precision component comprising the LAS glass ceramic according to the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In the attached figure:

[0028] Figure 1 The CTE-T curve of a material known from the prior art with low thermal expansion, for example for precision components, is shown.

[0029] Figure 2 The hysteresis behavior of three glass ceramic samples determined using the same method as used in the present invention is shown. This figure is from R. Jedamzik ​​et al., "Glass Ceramics Modeling of Thermal Expansion Behavior at Arbitrary Temperature Profiles”, Proc. SPIE, Vol. 7739, 2010.

[0030] Figures 3 to 8Hysteresis curves are shown for known glass-ceramic materials which can be used to manufacture known precision components and which have a thermal hysteresis of >0.1 ppm at least in the temperature range 10-35°C (dashed line = cooling curve, dots = heating curve).

[0031] Fig. 9 The hysteresis curve of a prior art glass ceramic is shown (dashed line = cooling curve, dots = heating curve), which can be used to manufacture precision components and has a thermal hysteresis of <0.1 ppm at least in the temperature range of 10-35°C. However, the steep curve shows that the glass ceramic is not zero expansion.

[0032] Figures 10 to 12 The hysteresis curves of the glass ceramics according to the present invention (according to the compositions of Examples 2, 6 and 7 in Table 1) are shown, which can be used to manufacture precision components according to the present invention, respectively, and which have a thermal hysteresis of <0.1 ppm at least in the temperature range of 10-35°C (dashed line = cooling curve, dot = heating curve).

[0033] Fig.13 A standardized Δl / l of the glass ceramic according to the invention (according to the composition of Example 7 in Table 1) is shown. 0 -T curve (also known as dl / l 0 curve) and an auxiliary line for determining the parameter F as a measure of the flatness of the expansion curve in the temperature range of 0°C to 50°C.

[0034] Fig.14 Another standardized Δl / l of a glass ceramic according to the invention (according to the composition of Example 7 in Table 1) based on another ceramization is shown. 0 -T curve and for determining the alternative parameter f as a measure of the flatness of the expansion curve in the temperature range from 20°C to 70°C (20;70) Auxiliary lines.

[0035] Fig.15 A standardized Δl / l of the glass ceramic according to the invention (according to the composition of Example 6 in Table 1) is shown. 0 -T curve (also known as dl / l 0 curve) and for determining the alternative parameter f as a measure of the flatness of the expansion curve in the temperature range of -10°C to 30°C (-10;30) Auxiliary lines.

[0036] Figures 16 to 19 The normalized Δl / l for known materials is shown 0-T curves, these materials can be used to manufacture known precision components, and auxiliary lines for determining the parameter F as a measure of the flatness of the expansion curve in the temperature range from -20°C or -10°C to 70°C or 80°C.

[0037] Fig. 20 The normalized Δl / l for known materials in the temperature range -20°C to +70°C is shown. 0 -T curve.

[0038] Fig.21 , 23 25 show that the CTE-T curve of the glass ceramics (according to the compositions of Examples 6, 7 and 9 in Table 1) that can be used to manufacture advantageous precision parts according to the present invention advantageously has a CTE "plateau".

[0039] Fig. 22 and Fig.24 Shows Fig.21 and Fig.23 details.

[0040] Fig.26 and 27 The slopes of the CTE-T curves of the glass ceramics having the compositions according to Example 6 and Example 7 in Table 1 are shown.

[0041] Fig.28 and 29 Different expansion curves set by different ceramizing parameters of the glass ceramics of the present invention having the compositions according to Example 6 and Example 7 in Table 1 are shown. DETAILED DESCRIPTION

[0042] The subject of the present invention is a LAS glass ceramic having a maximum temperature of 0±0.1×10 -6 / K and a thermal hysteresis of <0.1 ppm at least in the temperature range of 10-35 °C, and comprises the following components (in Mol % based on oxides):

[0043] SiO 2 60–71

[0044] Li 2 O 7–9.4

[0045] MgO+ZnO 0–<0.6

[0046] Choose from P 2 O 5 , R 2 At least one component of the group consisting of O and RO, wherein R 2 O can be Na 2 O and / or K2 O and / or Cs 2 O and / or Rb 2 O, and RO can be CaO and / or BaO and / or SrO, the content of the nucleating agent is 1.5 to 6 Mol%, wherein the nucleating agent is selected from TiO 2 、ZrO 2 、 2 O 5 , Nb 2 O 5 SnO 2 、MoO 3 , WO 3 , HfO 2 At least one component of the group consisting of

[0047] Among them, LAS glass ceramics contain up to 0.05Mol% As 2 O 3 .

[0048] The present invention provides for the first time a LAS glass ceramic (hereinafter also referred to as glass ceramic) which combines a number of relevant properties: its average coefficient of thermal expansion CTE in the range of 0 to 50°C is up to 0±0.1×10 -6 / K, i.e. it is zero expansion. In addition, it has a thermal hysteresis of <0.1ppm at least in the temperature range of 10°C to 35°C. Materials with a low hysteresis effect of <0.1ppm in the temperature range are referred to as "hysteresis-free" hereinafter. Since, as mentioned above, the form of the hysteresis depends on the temperature change rate used to determine the hysteresis, the statements about hysteresis within the scope of the present invention relate to a heating / cooling rate of 36K / h, i.e. 0.6K / min. In an advantageous embodiment, the LAS glass ceramic may have no hysteresis at least in the temperature range of 5°C to 35°C or at least 5°C to 40°C, advantageously at least in the temperature range of >0°C to 45°C, preferably at least in the temperature range of -5°C to 50°C.

[0049] Furthermore, the zero-expansion and hysteresis-free glass ceramics according to the invention contain up to 0.05 mol% of As 2 O 3 Advantageously, As in glass ceramics 2 O 3 The content of As is ≤0.04 Mol%, preferably ≤0.03 Mol%, preferably ≤0.025 Mol%, preferably ≤0.02 Mol%, preferably ≤0.015 Mol%. When the glass ceramic contains as little As as possible, 2 O 3 A particularly preferred variant of the glass ceramic is essentially As-free. 2 O3 Of which "basically no As 2 O 3 or no As" refers to the component As 2 O 3 It is not intentionally added as a component, but is included as an impurity at most, and there is no As 2 O 3 Glass ceramics for As 2 O 3 The impurity limit is ≤0.01 Mol%, preferably ≤0.005 Mol%. According to a special embodiment, the glass ceramic does not contain As 2 O 3 .

[0050] The following is a detailed introduction to CTE and thermal hysteresis characteristics.

[0051] According to the present invention, glass ceramics are understood to mean inorganic non-porous materials with a crystalline phase and a glass phase, wherein the matrix, i.e. the continuous phase, is usually a glass phase. In order to manufacture glass ceramics, the components of the glass ceramics are first mixed, melted and clarified, and then cast into so-called green glass (Grünglas). After cooling, the green glass is crystallized in a controlled manner by reheating (so-called "controlled volume crystallization"). The chemical composition (analysis) of green glass and the glass ceramics made therefrom is the same, and ceramicization only changes the internal structure of the material. Therefore, when the composition of glass ceramics is discussed below, the above content also applies to the precursor of the glass ceramics, i.e. green glass.

[0052] It was recognized within the scope of the present invention that the components MgO and ZnO promote the occurrence of thermal hysteresis in the temperature range under consideration, and that it is therefore necessary to limit the content of MgO and ZnO in order to provide a hysteresis-free, zero-expansion LAS glass ceramic at least in the temperature range of 10° C. to 35° C., as described in the claims. In contrast, the starting point previously was that these glass components were necessary in combination or separately in a zero-expansion LAS glass ceramic in order to achieve zero expansion and a “flat” CTE-T curve of the material, i.e. a low CTE-T curve slope in the relevant temperature range. Thus, a conflict of objectives arises in terms of the LAS glass ceramic being able to be zero-expansion or hysteresis-free.

[0053] If not only MgO and ZnO are substantially avoided, but also SiO is selected from the range specified in the present invention 2 and Li 2 O content, the present invention solves this conflict of objectives. It was found within the scope of the present invention that in SiO 2 (60-71Mol%) and Li 2O (7-9.4Mol%), even if the glass ceramics are clarified in an environmentally friendly manner, i.e., a maximum of 0.05Mol% As 2 O 3 content and preferably substantially free of As 2 O 3 In this case, surprisingly, zero-expansion and hysteresis-free glass-ceramics can be obtained.

[0054] The LAS glass ceramics contain a negative expansion crystalline phase, which within the scope of the present invention advantageously comprises or consists of a high quartz mixed crystal (also referred to as β-eucryptite) and a positive expansion glass phase. In addition to SiO 2 and Al 2 O 3 , Li 2 O is the main component of the mixed crystal. If present, ZnO and / or MgO will also be incorporated into the mixed crystal and react with Li 2 O together with the expansion behavior of the crystalline phase. This means that by the above provisions according to the invention (reduction, preferably exclusion of MgO and ZnO and a maximum of 0.05 mol% As 2 O 3 ) has a significant influence on the type and properties of the mixed crystals formed during the ceramizing process and on the composition of the remaining glass phase. Compared to known zero-expansion glass ceramics, in which MgO and ZnO are used in particular to adjust the desired expansion behavior of the glass ceramic, within the scope of the present invention, a selected material selected from the group consisting of P 2 O 5 , R 2 At least one component of the group consisting of O and RO, wherein R 2 O can be Na 2 O and / or K 2 O and / or Cs 2 O and / or Rb 2 O, and RO may be CaO and / or BaO and / or SrO. However, unlike MgO and ZnO, the above alkaline earth metal oxides and alkali metal oxides (if present) remain in the glass phase and are not incorporated into the high quartz mixed crystal.

[0055] It was found within the scope of the present invention that if the composition satisfies the condition that the molar content SiO 2 +(5x molar content Li 2 O)≥106 or preferably ≥106.5, preferably molar content SiO 2 +(5x molar content Li 2 O) ≥ 107 or ≥ 107.5, it is advantageous to provide a zero expansion and hysteresis-free glass ceramic. Alternatively or additionally, for the condition "molar content SiO 2 +(5x molar content Li 2O)" may be applied with a favorable upper limit of ≤115.5 or ≤114.5 or ≤113.5.

[0056] In an advantageous development, the glass ceramic may contain the following components in mol %, alone or in any combination:

[0057]

[0058]

[0059] Furthermore, preferably, in the glass ceramic within the above-mentioned limit range, R 2 O, RO and TiO 2 +ZrO 2 The sum may contain the following components in Mol% individually or in any combination:

[0060]

[0061] In an advantageous embodiment, the LAS glass-ceramic comprises (in Mol % based on oxides):

[0062] The nucleating agent is preferably TiO 2 and / or ZrO 2 .

[0063] In an advantageous embodiment, the LAS glass-ceramic comprises (in Mol % based on oxides):

[0064]

[0065]

[0066] The nucleating agent is preferably TiO 2 and / or ZrO 2 .

[0067] In a further advantageous embodiment, the LAS glass ceramic comprises (in Mol % based on oxides):

[0068] The nucleating agent is preferably TiO 2 and / or ZrO 2 .

[0069] The glass ceramic contains at least 60 Mol%, more preferably at least 60.5 Mol%, further preferably at least 61 Mol%, further preferably at least 61.5 Mol%, and more preferably at least 62.0 Mol% of silicon dioxide (SiO 2 ).SiO 2The content of SiO is up to 71 Mol% or less, more preferably up to 70 Mol% or less, more preferably up to 69 Mol%, and further preferably up to 68.5 Mol%. 2 The mixture is more difficult to melt and the viscosity of the melt is higher, which may lead to homogenization problems of the melt in large-scale production facilities. Therefore, a content of 71 mol%, preferably 70 mol%, should not be exceeded. If the viscosity of the melt is high, the processing temperature Va of the melt increases. Clarification and homogenization of the melt require very high temperatures, which, however, result in the lining (Auskleidung) of the melting unit being attacked by the aggressiveness of the melt, which increases with increasing temperature. In addition, even higher temperatures may not be sufficient to produce a homogeneous melt, with the result that the green glass may have streaks and inclusions (in particular bubbles and particles from the lining of the melting unit), so that after ceramicization, the uniformity requirements of the properties of the produced glass-ceramic, such as the uniformity of the coefficient of thermal expansion, are not met. Lower SiO 2 The content as the upper limit may be preferred for this reason.

[0070] Al 2 O 3 The content of Al is advantageously at least 10 Mol%, preferably at least 11 Mol%, preferably at least 12 Mol%, more preferably at least 13 Mol%, further preferably at least 14 Mol%, further preferably at least 14.5 Mol%, more preferably at least 15 Mol%. If the content is too low, no or too little low expansion mixed crystals are formed. 2 O 3 The proportion of Al is advantageously at most 22 Mol%, preferably at most 21 Mol%, preferably at most 20 Mol%, further preferably at most 19.0 Mol%, more preferably at most 18.5 Mol%. 2 O 3 Too high a content will lead to an increase in viscosity and promote uncontrolled devitrification of the material.

[0071] The glass ceramics according to the present invention may contain 0 to 6 mol% of P 2 O 5 . Phosphate content of glass ceramics 2 O 5 It may be advantageously at least 0.1 Mol%, preferably at least 0.3 Mol%, preferably at least 0.5 Mol%, further preferably at least 0.6 Mol%, more preferably at least 0.7 Mol%, more preferably at least 0.8 Mol%. 2 O 5 It is essentially embedded in the crystal phase of the glass ceramic and has a positive influence on the expansion behavior of the crystal phase and thus the expansion behavior of the glass ceramic. In addition, the melting of the components and the clarification behavior of the melt are improved. However, if P2 O 5 If the content is too much, the trend of the CTE-T curve in the temperature range from 0°C to 50°C does not show a favorable flat trend. Therefore, advantageously, the P content is up to 6 Mol%, preferably up to 5 Mol%, more preferably up to 4 Mol%, and more preferably less than 4 Mol%. 2 O 5 According to various embodiments, the glass ceramic may not contain P 2 O 5 .

[0072] In the context of the present invention, the component SiO 2 、Al 2 O 3 and / or P 2 O 5 , that is, a specific sum and ratio of the components forming high quartz mixed crystals are favorable for forming the glass ceramic according to the invention.

[0073] The basic components of LAS glass ceramics, SiO 2 and Al 2 O 3 The total proportion in mol% of the components SiO is advantageously at least 75 mol%, preferably at least 78 mol%, preferably at least 79 mol%, more preferably at least 80 mol% and / or preferably up to 90 mol%, preferably up to 87 mol%, preferably up to 86 mol%, more preferably up to 85 mol%. If this sum is too high, the viscosity curve of the melt is shifted to higher temperatures, which is disadvantageous, as already mentioned above for the component SiO 2 If the total amount is too low, too few mixed crystals are formed.

[0074] The basic components of LAS glass ceramics, SiO 2 、Al 2 O 3 and P 2 O 5 The total proportion in Mol% is preferably at least 77 Mol%, advantageously at least 81 Mol%, advantageously at least 83 Mol%, more preferably at least 84 Mol% and / or preferably at most 91 Mol%, advantageously at most 89 Mol%, more preferably at most 87 Mol%, according to a variant at most 86 Mol%.

[0075] P 2 O 5 With SiO 2 The ratio of the Mol% content of 2-Hg to 2-Hg is preferably at least 0.005, advantageously at least 0.01, preferably at least 0.012 and / or preferably at most 0.1, more preferably at most 0.08, according to a variant at most 0.07.

[0076] As a further component, the glass ceramic contains lithium oxide (Li2O3) in a proportion of at least 7 mol%, advantageously at least 7.5 mol%, preferably at least 8 mol%, particularly preferably at least 8.25 mol%. 2 O) Li 2 The proportion of O is limited to a maximum of 9.4 Mol%, more preferably a maximum of 9.35 Mol%, further preferably a maximum of or less than 9.3 Mol%. Li 2 O is a component of the mixed crystal phase and contributes significantly to the thermal expansion of the glass ceramic. The upper limit of 9.4 mol% must not be exceeded, otherwise a glass ceramic with a negative thermal expansion coefficient CTE (0; 50) will result. 2 If the O content is less than 7 mol%, too few mixed crystals are formed and the CTE of the glass-ceramic remains positive.

[0077] Glass ceramics can contain at least one alkaline earth metal oxide selected from the group consisting of CaO, BaO, SrO, wherein the group is collectively referred to as "RO". Components from the RO group are substantially retained in the amorphous glass phase of glass ceramics, and can be very important for maintaining zero expansion of ceramicized materials. If the sum of CaO+BaO+SrO is too high, the target CTE (0; 50) according to the present invention cannot be achieved. The ratio of RO is therefore advantageously up to 6Mol% or up to 5.5Mol%, preferably up to 5Mol%, advantageously up to 4.5Mol%, preferably up to 4Mol%, preferably up to 3.8Mol%, further preferably up to 3.5Mol%, also preferably up to 3.2Mol%. If glass ceramics include RO, a favorable lower limit can be at least 0.1Mol%, advantageously at least 0.2Mol%, preferably at least 0.3Mol%, also preferably at least 0.4Mol%. According to various embodiments, glass ceramics can be free of RO.

[0078] The content of CaO can be preferably up to 5 Mol%, advantageously up to 4 Mol%, advantageously up to 3.5 Mol%, advantageously up to 3 Mol%, more preferably up to 2.8 Mol%, more preferably up to 2.6 Mol%. The glass ceramic can advantageously contain at least 0.1 Mol%, advantageously at least 0.2 Mol%, preferably at least 0.4 Mol%, preferably at least 0.5 Mol% of CaO. The glass ceramic can advantageously contain the component BaO, which is a good glass former, in an amount of at least 0.1 Mol%, preferably at least 0.2 Mol% and / or up to 4 Mol%, advantageously up to 3 Mol%, advantageously up to 2.5 Mol%, preferably up to 2 Mol%, preferably up to 1.5 Mol%, and also preferably up to 1.4 Mol%. The glass ceramic may contain SrO in a content of up to 3 Mol%, advantageously up to 2 Mol%, preferably up to 1.5 Mol%, preferably up to 1.3 Mol%, preferably up to 1.1 Mol%, more preferably up to 1 Mol%, also preferably up to 0.9 Mol% and / or preferably at least 0.1 Mol%. According to various embodiments, the glass ceramic is free of CaO and / or BaO and / or SrO.

[0079] Sodium oxide (Na 2 O) and / or potassium oxide (K 2 O) and / or cesium oxide (Cs 2 O) and / or rubidium oxide (Rb 2 O) is optionally contained in the glass ceramic, i.e., Na-free 2 O and / or no K 2 O and / or no Cs 2 O and / or no Rb 2 Variations of O are possible. 2 The content of O may advantageously be up to 3 Mol%, preferably up to 2 Mol%, preferably up to 1.7 Mol%, preferably up to 1.5 Mol%, preferably up to 1.3 Mol%, preferably up to 1.1 Mol%. 2 The content of O may advantageously be up to 3 Mol%, preferably up to 2.5 Mol%, preferably up to 2 Mol%, preferably up to 1.8 Mol%, preferably up to 1.7 Mol%. Cs 2 The content of O may advantageously be up to 2 Mol%, preferably up to 1.5 Mol%, preferably up to 1 Mol%, preferably up to 0.6 Mol%. Rb 2 The content of O can advantageously be up to 2 Mol%, preferably up to 1.5 Mol%, preferably up to 1 Mol%, preferably up to 0.6 Mol%. According to a specific embodiment, the glass ceramic contains no Na 2 O and / or K 2 O and / or Cs 2 O and / or Rb2 O.

[0080] Na 2 O.K 2 O、Cs 2 O、Rb 2 O may be contained in the glass ceramics in a proportion of at least 0.1 mol%, preferably at least 0.2 mol%, more preferably at least 0.5 mol%, respectively and independently of one another. 2 O.K 2 O、Cs 2 O、Rb 2 O essentially remains in the amorphous glass phase of the glass-ceramic and may be very important for maintaining zero expansion of the ceramized material.

[0081] Therefore, Na 2 O.K 2 O、Cs 2 O、Rb 2 The sum of the contents of O and R 2 O may advantageously be at least 0.1 Mol%, preferably at least 0.2 Mol%, advantageously at least 0.3 Mol%, preferably at least 0.4 Mol%. Advantageously at least 0.2 Mol% of low R 2 O content can help increase the temperature range in which the glass-ceramic expansion curve is flat. 2 O.K 2 O、Cs 2 O、Rb 2 The sum of the contents of O and R 2 O may advantageously be at most 6 Mol%, preferably at most 5 Mol%, preferably at most 4 Mol%, preferably at most 3 Mol%, preferably at most 2.5 Mol%. If Na 2 O+K 2 O+Cs 2 O+R 2 If the sum of R O is too low or too high, the target CTE (0; 50) according to the present invention may not be achieved. 2 O.

[0082] The glass ceramic may contain a maximum of 0.35 mol% of magnesium oxide (MgO). Further advantageous upper limits may be a maximum of 0.3 mol%, a maximum of 0.25 mol%, a maximum of 0.2 mol%, a maximum of 0.15 mol%, a maximum of 0.1 mol% or a maximum of 0.05 mol%. The glass ceramic according to the invention is particularly preferably free of MgO. As described above, the MgO component in the glass ceramic causes thermal hysteresis in a temperature range of 0°C to 50°C. The less MgO the glass ceramic contains, the smaller the hysteresis in a specified temperature range.

[0083] The glass ceramic may contain a maximum of 0.5 Mol% zinc oxide (ZnO). Another advantageous upper limit may be a maximum of 0.45 Mol%, a maximum of 0.4 Mol%, a maximum of 0.35 Mol%, a maximum of 0.3 Mol%, a maximum of 0.25 Mol%, a maximum of 0.2 Mol%, a maximum of 0.15 Mol%, a maximum of 0.1 Mol% or a maximum of 0.05 Mol%. The glass ceramic according to the present invention is particularly preferably free of ZnO. As described above as the inventor's discovery, the ZnO component in the glass ceramic causes thermal hysteresis in a temperature range of 0°C to 50°C. The less ZnO the glass ceramic contains, the smaller the hysteresis in the specified temperature range.

[0084] It is important for the hysteresis-free property of the glass ceramic according to the invention that the condition of less than 0.6 mol% of MgO+ZnO is met. Another advantageous upper limit of the sum of MgO+ZnO can be a maximum of 0.55 mol%, a maximum of 0.5 mol%, less than 0.5 mol%, a maximum of 0.45 mol%, a maximum of 0.4 mol%, a maximum of 0.35 mol%, a maximum of 0.3 mol%, a maximum of 0.25 mol%, a maximum of 0.2 mol%, a maximum of 0.15 mol%, a maximum of 0.1 mol% or a maximum of 0.05 mol%.

[0085] The glass ceramic further comprises a 2 、ZrO 2 、 2 O 5 , Nb 2 O 5 SnO 2 、MoO 3 , WO 3 , HfO 2 At least one crystal nucleating agent from the group consisting of. The nucleating agent may be a combination of two or more of the above components. The sum of the proportions of the nucleating agents is preferably at least 1.5 Mol%, preferably at least 2 Mol% or more than 2 Mol%, more preferably at least 2.5 Mol%, and according to some variants at least 3 Mol%. The upper limit may be up to 6 Mol%, preferably up to 5 Mol%, preferably up to 4.5 Mol% or up to 4 Mol%. In a particularly advantageous variant, the upper and lower limits mentioned apply to the TiO 2 and ZrO 2 The sum of .

[0086] The glass ceramic may preferably contain titanium dioxide (TiO2) in an amount of at least 0.1 Mol%, advantageously at least 0.5 Mol%, preferably at least 1.0 Mol%, preferably at least 1.5 Mol%, preferably at least 1.8 Mol% and / or preferably up to 5 Mol%, advantageously up to 4 Mol%, more preferably up to 3 Mol%, further preferably up to 2.5 Mol%, preferably 2.3 Mol%. 2 ). The glass ceramic according to the present invention is free of TiO 2 Variations are possible.

[0087] The glass ceramic may also advantageously contain zirconium oxide (ZrO) in a content of up to 3 mol%, preferably up to 2.5 mol%, more preferably up to 2 mol%, preferably up to 1.5 mol% or up to 1.2 mol%. 2 ). ZrO may be contained preferably in an amount of at least 0.1 Mol%, more preferably at least 0.5 Mol%, at least 0.8 Mol%, or at least 1.0 Mol%. 2 The glass ceramic according to the invention is free of ZrO 2 Variations are possible.

[0088] According to some advantageous variants of the present invention, Ta may be contained in the glass ceramic alone or in total in an amount of 0 to 5 mol%. 2 O 5 and / or Nb 2 O 5 and / or SnO 2 and / or MoO 3 and / or WO 3 and / or HfO 2 And for example, it is used as an alternative or additional nucleating agent or for adjusting optical properties, such as the refractive index. In order to adjust the optical properties, in some advantageous variants, for example Gd 2 O 3 , Y 2 O 3 , HfO 2 、Bi2O 3 and / or GeO 2 .

[0089] Although the desired internal quality, especially with a few bubbles and few striations, is reduced in As 2 O 3 As content or no As 2 O 3 In order to provide the hysteresis-free and zero-expansion glass ceramic according to the invention, in an advantageous embodiment at least one chemical refining agent is used.

[0090] In an advantageous embodiment, instead of As 2 O3 Except for a small amount of As 2 O 3 In addition to As (up to 0.05 mol %), the glass ceramic may also have at least one alternative redox refining agent and / or at least one evaporative refining agent and / or at least one decomposition refining agent as a chemical refining agent. 2 O 3 It is also a redox clarifier. The present invention is used as As 2 O 3 Alternative or supplemental redox fining agents are also referred to as "alternative redox fining agents".

[0091] In an advantageous variant, the total content of chemical refining agents that can be detected in the glass ceramic (if As 2 O 3 Present in glass ceramics, excluding As 2 O 3 In one advantageous embodiment, the total content of the fining agent detectable in the glass ceramic (excluding As 2 O 3 ) more than 0.01 mol%, preferably at least 0.05 mol%, preferably at least 0.1 mol%, preferably at least 0.15 mol%, advantageously at least 0.2 mol% and / or up to 1 mol%, preferably up to 0.7 mol%, preferably up to 0.5 mol%, preferably up to 0.4 mol%. Some advantageous variants may also contain up to 0.3 mol%, preferably up to 0.25 mol% or up to 0.2 mol% of refining agent. The proportions of the respective components can be determined by analyzing the glass ceramic. This applies in particular to all of the refining agents mentioned below, except for the sulfate components mentioned.

[0092] Redox fining agents contain multivalent or polyvalent ions which can occur in at least two oxidation states which are in a temperature-dependent equilibrium with one another, wherein at high temperatures a gas, usually oxygen, is released. Thus, certain multivalent metal oxides can be used as redox fining agents. In an advantageous variant, the alternative redox fining agent can include a metal selected from the group consisting of Sb 2 O 3 SnO 2 、CeO 2 、MnO 2 , Fe 2 O 3In principle, however, other redox compounds are also suitable if they release their refining gas in the temperature range relevant for refining and are converted into oxide or metallic forms of metal ions with different valence states. For example, many such compounds are described in DE 19939771 A. Preference is given to alternative redox refining agents, such as Sb 2 O 3 SnO 2 、CeO 2 , which releases refined gases, especially oxygen, at temperatures below 1700°C.

[0093] By analyzing glass ceramics, As 2 O 3 The content of 20% and / or the content of at least one alternative redox fining agent, from which the person skilled in the art can draw conclusions about the type and amount of fining agent used. The alternative redox fining agent can be added to the mixture, for example as an oxide.

[0094] In an advantageous variant, the total content of alternative redox fining agents may be in the range of 0 mol% to 1 mol%. In an advantageous embodiment, the total content of alternative redox fining agents detectable in the glass ceramic exceeds 0.01 mol%, preferably at least 0.05 mol%, preferably at least 0.1 mol%, preferably at least 0.15 mol%, advantageously at least 0.2 mol% and / or at most 1 mol%, preferably at most 0.7 mol%, preferably at most 0.5 mol%, preferably at most 0.4 mol%. Some advantageous variants may also contain at most 0.3 mol%, preferably at most 0.25 mol% or at most 0.2 mol% of alternative redox fining agents.

[0095] As an alternative redox fining agent, the glass ceramic may contain 0 mol% to 1 mol% antimony oxide (Sb 2 O 3 In an advantageous embodiment, the glass ceramic contains Sb in a content of greater than 0.01 Mol%, preferably at least 0.05 Mol%, advantageously at least 0.1 Mol%, advantageously at least 0.15 Mol%, preferably at least 0.2 Mol% and / or preferably at most 1 Mol%, advantageously at most 0.7 Mol%, more preferably at most 0.5 Mol%, further preferably at most 0.4 Mol%, preferably at most 0.3 Mol%. 2 O 3 . Due to Sb 2 O 3 Considered harmful to the environment, use as little Sb as possible 2 O 3It may be advantageous to refine the glass ceramic. Preferred embodiments of the glass ceramic are substantially free of Sb. 2 O 3 or Sb-free, wherein "substantially no Sb 2 O 3 " indicates Sb 2 O 3 It is not intentionally added to the composition as a raw material component, but is at most included as an impurity, and there is no Sb 2 O 3 The impurity limit of the glass ceramic is a maximum of 0.01 mol%, preferably a maximum of 0.005 mol%. According to a specific embodiment, the glass ceramic is free of Sb. 2 O 3 .

[0096] As an alternative redox fining agent, the glass ceramic may contain 0 mol% to 1 mol% of tin oxide (SnO 2 In an advantageous embodiment, the glass ceramic contains SnO in a content of greater than 0.01 Mol%, preferably at least 0.05 Mol%, advantageously at least 0.1 Mol%, advantageously at least 0.15 Mol%, preferably at least 0.2 Mol%, preferably at least 0.3 Mol% and / or preferably at most 1 Mol%, advantageously at most 0.7 Mol%, more preferably at most 0.6 Mol%. 2 In some variants, an upper limit of at most 0.5 Mol %, more preferably at most 0.4 Mol %, preferably at most 0.3 Mol % may be advantageous. 2 The content of SnO is too high, and it is possible that the ceramicization process of green glass is more difficult to control, because SnO 2 At higher contents, it acts not only as a fining agent but also as a crystal nucleating agent. 2 Sn-free or Sn-free variants are possible and advantageous, i.e. no Sn-containing raw materials are added to the mixture for refining the base green glass, wherein the SnO introduced by the raw materials or the process is 2 The limit of impurities is maximum 0.01 Mol %, preferably maximum 0.005 Mol %.

[0097] As an alternative redox fining agent, the glass ceramic may contain 0 Mol% to 1 Mol% CeO 2 and / or MnO 2 and / or Fe 2 O 3These components may each and independently of one another preferably be present in a content of more than 0.01 mol%, preferably at least 0.05 mol%, advantageously at least 0.1 mol%, advantageously at least 0.15 mol%, preferably at least 0.2 mol% and / or preferably at most 1 mol%, advantageously at most 0.7 mol%, more preferably at most 0.5 mol%, more preferably at most 0.4 mol%, preferably at most 0.3 mol%. Preferred variants of the glass ceramic contain no CeO 2 and / or MnO 2 and / or Fe 2 O 3 , i.e. no Ce-containing raw material and / or Mn-containing raw material and / or Fe-containing raw material is added to the mixture for refining the basic green glass, wherein the CeO introduced by the raw materials or the process 2 and / or MnO 2 and / or Fe 2 O 3 The limit of impurities is maximum 0.01 Mol %, preferably maximum 0.005 Mol %.

[0098] The evaporative clarifier is a component that evaporates due to its vapor pressure at high temperature, allowing the gas formed in the melt to play a clarifying role.

[0099] In an advantageous variant, the evaporative refining agent can have a halogen component.

[0100] In an advantageous variation, the evaporation clarifier may include at least one halogen with a clarification effect, particularly selected from the group consisting of chlorine (Cl), bromine (Br) and iodine (I). The preferred halogen with a clarification effect is chlorine. Fluorine is not a halogen with a clarification effect because it has volatilized at too low a temperature. The glass ceramic may still contain fluorine. However, fluorine reduces the transparency of the glass ceramic, so the component (if it should be present) is preferably limited to a maximum of 0.5 Mol%, preferably a maximum of 0.3 Mol%, preferably a maximum of 0.1 Mol%. The glass ceramic preferably does not contain fluorine.

[0101] Halogens with a clarifying effect can be added in various forms. In one embodiment, they are added to the mixture as salts with alkali metal cations or alkaline earth metal cations, or as aluminum halides. In one embodiment, the halogen is used in the form of a salt and the cations in the salt correspond to the cations present in the glass ceramic as oxides. Halogens with a clarifying effect can be used in the form of halogen compounds, in particular halides. Suitable halides are in particular salts of chloride anions, bromide anions and / or iodide anions with alkali metal cations or alkaline earth metal cations or aluminum cations. Preferred examples are chlorides, such as LiCl, NaCl, KCl, CaCl 2 、BaCl 2、SrCl 2 、AlCl 3 and combinations thereof. The corresponding bromides and iodides such as LiBr, LiI, NaBr, NaI, KBr, KI, CaI 2 , CaBr 2 and combinations thereof are also possible. Other examples are BaBr 2 ,BaI 2 , SrBr 2 , SrI 2 and combinations thereof.

[0102] In a favorable variation, the total content of halogens with a clarifying effect (i.e., Cl and / or Br and / or I) can be in the range of 0 Mol% to 1 Mol%. In a favorable embodiment, the total content of halogens with a clarifying effect detectable in the glass ceramic is greater than 0.03 Mol%, preferably at least 0.04 Mol%, preferably at least 0.06 Mol%, preferably at least 0.08 Mol%, preferably at least 0.1 Mol%, preferably at least 0.15 Mol%, advantageously at least 0.2 Mol% and / or up to 1 Mol%, preferably up to 0.7 Mol%, preferably up to 0.5 Mol%, preferably up to 0.4 Mol%. Some favorable variations can also include up to 0.3 Mol%, preferably up to 0.25 Mol% or up to 0.2 Mol% of halogens with a clarifying effect. The so-called content relates to the amount of halogen that can be detected in the glass ceramic. Those skilled in the art are familiar with using this information to calculate the amount of halogen compounds or halides required for clarification.

[0103] The glass ceramic may contain 0 Mol% to 1 Mol% chlorine (determined atomically and given as Cl). In an advantageous embodiment, the glass ceramic contains Cl in an amount greater than 0.03 Mol%, advantageously at least 0.04 Mol%, advantageously at least 0.05 Mol%, advantageously at least 0.1 Mol%, advantageously at least 0.15 Mol%, preferably at least 0.2 Mol% and / or preferably up to 1 Mol%, advantageously up to 0.7 Mol%, more preferably up to 0.5 Mol%, further preferably up to 0.4 Mol%, preferably up to 0.3 Mol%. Some advantageous glass ceramics may be Cl-free, i.e. no Cl-containing raw materials are added to the mixture to clarify the basic green glass. Cl is present at most in the form of impurities, wherein the upper limit of the Cl impurity is 0.03 Mol%.

[0104] The same ranges and restrictions mentioned apply to Br as halogen with a clarifying effect. The same ranges and restrictions mentioned apply to I as halogen with a clarifying effect. Preferred variants of the glass ceramic contain no Br and / or I.

[0105] As an alternative or supplement to the evaporative fining agent and / or the alternative redox fining agent, the chemical fining agent may include at least one decomposition fining agent. The decomposition fining agent is an inorganic compound that decomposes at high temperature and releases a fining gas, and the decomposition product has a sufficiently high gas pressure, especially greater than 105 Pa. The decomposition fining agent may preferably be a salt containing an oxygen anion, especially a sulfate component. Preferably, the decomposition fining agent contains a sulfate component. By decomposing the component added in the form of sulfate, SO4, which helps to clarify the melt, is released at high temperature. 2 and O 2 gas.

[0106] The sulfate component can be added in various forms. In one embodiment, it is added to the mixture as a salt with an alkali metal or alkaline earth metal cation. In one embodiment, the sulfate is used in the form of a salt and the cations in the salt correspond to the cations present in the glass ceramic as oxides. For example, the following components can be advantageously used as sulfate sources: Li 2 SO 4 、Na 2 SO 4 , K 2 SO 4 、CaSO 4 ,BaSO 4 、SrSO 4 .

[0107] In the context of the present invention, sulfate is defined as SO in the material analysis. 3 However, since the solubility of sulfate in LAS glass ceramics is very low, the sulfate component (i.e., SO 3 ) can no longer be detected using standard X-ray fluorescence analysis. Therefore, in the sulfate fining example (see below), it is determined how much Mol% SO is used based on the synthesis of the glass melt. 4 or Mol%SO 3 For example, the residual gas content (SO 2 ) Determine the sulfate component used as a fining agent.

[0108] Advantageously, the glass ceramics which have been refined with a sulfate component are prepared by adding more than 0.01 mol%, preferably at least 0.05 mol%, advantageously at least 0.1 mol%, advantageously at least 0.15 mol%, preferably at least 0.2 mol% and / or preferably at most 1 mol%, advantageously at most 0.7 mol%, more preferably at most 0.5 mol%, further preferably at most 0.4 mol%, preferably at most 0.3 mol% of SO during the synthesis by at least one corresponding sulfate compound. 3 . Does not contain sulfate (i.e. no SO3 or no SO 4 ) clarified glass ceramics are possible and advantageous. Therefore, the content of sulfate with a clarifying effect added in the synthesis of glass ceramics can be between 0 Mol% and 1 Mol% SO 3 within the range.

[0109] According to a variant of the invention, the glass ceramic or the glass on which it is based can be refined using suitable metal sulfides as decomposition refining agents, for example, as described in US 2011 / 0098171 A. In one embodiment, the cations in the sulfide correspond to the cations present in the glass ceramic as oxides. Examples of suitable metal sulfides are alkali metal sulfides, alkaline earth metal sulfides and / or aluminum sulfides, which release SO in the melt under oxidizing conditions. 3 In order for the metal sulfide to be able to fully fulfill its role as a refining agent, it is advantageously used in combination with an oxidizing agent, preferably a nitrate and / or a sulfate.

[0110] With reduced As 2 O 3 Contains or advantageously contains no As 2 O 3 The glass ceramics can advantageously have a combination of chemical fining agents. In this case, the following combinations may be advantageous, wherein the corresponding glass ceramics preferably have the fining agents mentioned within the above limits for individual components and / or total amount. Advantageous embodiments include:

[0111] -SnO 2 and / or Sb 2 O 3 With a maximum of 0.05Mol%As 2 O 3 ;or

[0112] -No As 2 O 3 Combination, such as: Sb 2 O 3 with SnO 2 ; Sb 2 O 3 With Cl, Sb 2 O 3 with SO 3 ; or - No As 2 O 3 and Sb-free 2 O 3 Combination, such as: SnO 2 With Cl, SnO 2 with SO 3 , Cl and SO 3 .

[0113] Alternatively, glass ceramics which have been refined with only one refining agent may also be advantageous, for example containing only Sb 2 O 3 Or only containing SnO 2 Glass ceramics as fining agents.

[0114] As an alternative or supplement to the above-mentioned fining of the melt with chemical fining agents, the principle of this fining is to add compounds that decompose and release gases themselves or volatilize at higher temperatures or release gases at higher temperatures in equilibrium reactions. Known physical fining methods can also be used advantageously, such as reducing the viscosity of the glass melt by increasing the temperature, vacuum fining, high-pressure fining, etc.

[0115] In an advantageous variant of the invention, the mixture contains nitrates (NO 3 ), which acts as an oxidant during the melting and fining process and ensures that oxidizing conditions exist in the melt in order to increase the effectiveness of the fining agents used, in particular alternative redox fining agents. In one embodiment, the nitrate is used in the form of a salt and the cations in the salt correspond to the cations present in the glass ceramic as oxides. Examples of this can be: aluminum nitrate, alkali metal nitrates, alkaline earth metal nitrates, zirconium nitrate, but ammonium nitrate can also be used advantageously as a nitrate source. It is possible to use a nitrate compound or a mixture of several nitrate compounds. If a nitrate compound or a mixture of nitrate compounds is included in the mixture to support the fining process, then NO 3 - The sum of is preferably at least 0.4 Mol%, preferably at least 0.5 Mol%, preferably at least 0.8 Mol%, preferably at least 1 Mol% and / or advantageously up to 5 Mol%, preferably up to 4 Mol%. In some advantageous variants, up to 3 Mol% of nitrates can also be used. Due to the volatility of nitrates, nitrates can no longer be detected in the glass or glass ceramic.

[0116] The above glass composition can be added with colored oxides such as Nd if necessary. 2 O 3 , Fe 2 O 3 、CoO、NiO、V 2 O 5 、MnO 2 , CuO, CeO 2 , CR 2 O 3 , the rare earth oxide content, either individually or in total, is 0-3 mol%. A preferred variant contains no colored oxides.

[0117] B 2 O 3The transparency of the glass ceramic is negatively affected. Therefore, in an advantageous variant, the content of this component is limited to <0.2 mol%, preferably to a maximum of 0.1 mol%. The preferred variant does not contain B 2 O 3 .

[0118] According to an advantageous embodiment of the invention, the composition does not contain components not mentioned above.

[0119] According to an advantageous embodiment of the present invention, the glass ceramic or green glass according to the present invention is preferably composed of at least 90 Mol%, more preferably at least 95 Mol%, most preferably at least 99 Mol% of the above components or preferably of the component SiO 2 、Al 2 O 3 , Li 2 O.P 2 O 5 , R 2 O, RO and nucleating agent.

[0120] According to an advantageous refinement of the glass ceramic, it substantially does not contain any of the following: 2 O 3 One component or more components of the group consisting of Cr3, F, and Cd compounds.

[0121] According to the invention, the expression "free of X" or "free of component X" means that the glass ceramic is essentially free of this component X, i.e. this component is present in the glass at most as an impurity, but is not added to the composition as a separate component. With regard to impurities, in particular impurities with MgO and / or ZnO, in the variant free of MgO and / or free of ZnO, a limit of 0.03 mol%, preferably 0.01 mol%, based on the respective individual component should not be exceeded. In the case of other glass components, higher impurity contents of up to 0.1 mol%, preferably up to 0.05 mol%, advantageously up to 0.01 mol%, advantageously up to 0.005 mol%, advantageously up to 0.003 mol% for some components are possible for each component. X here represents any component, for example PbO. These stated limits are independent of the fining agents, for which specific impurity limits were described above.

[0122] The glass ceramic of the present invention has high quartz mixed crystals as the main crystalline phase. The main crystalline phase is the crystalline phase with the largest Vol% ratio in the crystalline phase. High quartz mixed crystals are a metastable phase that changes its composition and / or structure or transforms into different crystalline phases depending on the crystallization conditions. Mixed crystals containing high quartz have very low thermal expansion that even decreases with increasing temperature. In an advantageous embodiment, the crystalline phase does not contain β-spodumene and keatite.

[0123] Advantageous embodiments of LAS glass ceramics have a crystalline phase proportion of less than 70% by volume and / or advantageously greater than 45% by volume. The crystalline phase consists of high quartz mixed crystals, which are also referred to as β-eucryptite mixed crystals. The average crystallite size of the high quartz mixed crystals is advantageously <100nm, preferably <80nm, preferably <70nm. The small crystallite size means that the glass ceramic is transparent and can also be polished better. In a specific advantageous variant, the average crystallite size of the high quartz mixed crystals is ≤60nm, preferably ≤50nm. The crystalline phases, their proportions and average crystallite size are determined in a known manner by means of X-ray diffraction analysis.

[0124] According to one embodiment of the invention, a transparent glass ceramic is produced. Due to the transparency, many properties of this glass ceramic can be better evaluated, of course, especially its internal quality. The glass ceramics according to the invention are transparent, that is, they have an internal transmittance of at least 70% in the wavelength range of 350 to 650 nm. 2 O 3 The glass ceramics produced within the scope of the invention are free of pores and cracks. Within the scope of the invention, "free of pores" means a porosity of less than 1%, preferably less than 0.5%, more preferably less than 0.1%. Cracks are gaps in an otherwise continuous structure, i.e. discontinuities.

[0125] In order to be able to produce homogeneous glass ceramics in large-scale production facilities, it is advantageous if the green glass on which the glass ceramic is based (and therefore the glass ceramic) has a processing temperature Va of advantageously at most 1330° C., preferably at most 1320° C. Some advantageous variants may have a processing temperature of at most 1310° C. or at most 1300° C. or below 1300° C. The processing temperature Va is the temperature at which the melt viscosity is 10 4 dPas. In particular, homogeneity refers to the homogeneity of the CTE of the glass ceramic over large volumes as well as small numbers, preferably free of inclusions such as bubbles and particles. This is a quality feature of glass ceramics and a prerequisite for use in precision components, especially very large precision components.

[0126] The processing temperature is determined by the composition of the glass ceramic. In particular, due to the glass lattice forming component SiO 2 is considered to be the decisive component for increasing viscosity and thus processing temperature, so the maximum SiO 2 The content is selected according to the above regulations.

[0127] CTE

[0128] The glass ceramics according to the invention are zero-expansion (see Table 1), i.e. they have a maximum thermal expansion of 0±0.1×10 -6 / K average thermal expansion coefficient CTE. Some advantageous variants even have a CTE of 0±0.05×10 -6 For some applications, it may be advantageous if the average CTE is at most 0±0.1×10-10°C over a larger temperature range, for example in the range of -30°C to +70°C, preferably in the range of -40°C to +80°C. -6 / K, that is, there is zero expansion.

[0129] In order to determine the CTE-T curves of the glass ceramics and precision parts according to the present invention and the comparative examples, the differential CTE (T) is first determined. The differential CTE (T) is determined as a function of temperature. The CTE is then specified according to the following formula (1):

[0130]

[0131] To create the Δl / l of the test piece (glass ceramic or precision component) 0 -T curve or expansion curve or length change Δl / l against temperature 0 , the length variation of the test piece from an initial length l0 at an initial temperature t0 to a length lt at temperature t as a function of temperature can be measured. In this case, a small temperature interval of, for example, 5°C or 3°C or 1°C is preferably selected to determine the measuring point. For example, such a measurement can be performed by expansion measurement, interferometry, such as the Fabry-Perot method, i.e. evaluating the shift of the resonance peak of the laser beam coupled into the material, or other suitable methods. Within the scope of the present invention, an expansion measurement method with a temperature interval of 1°C is selected for a rod-shaped sample of a test piece with a length of 100 mm and a diameter of 6 mm to determine the CTE. The accuracy of the method selected for determining the CTE is preferably at least ±0.05 ppm / K, preferably at least ±0.03 ppm / K. Of course, the CTE can also be determined using a method with an accuracy of at least ±0.01 ppm / K, preferably at least ±0.005 ppm / K or, according to some embodiments, even at least ±0.003 ppm / K or at least ±0.001 ppm / K.

[0132] From Δl / l 0 The -T curve calculates the average CTE for a specific temperature range, such as the temperature range from 0°C to 50°C.

[0133] By deriving Δl / l 0-T curve to obtain the CTE-T curve. From the CTE-T curve, the zero crossing point and slope of the CTE-T curve within a temperature range can be determined. The form and position of the favorable CTE platform formed in some variations are determined based on the CTE-T curve (see below and Fig.21 , 23 and 25).

[0134] Advantageous embodiments of precision components comprising glass ceramics according to the invention (especially in the form of substrates) have a high CTE homogeneity. Here, the value of the CTE homogeneity (English: "total spatial variation of CTE") is understood as the so-called peak-to-valley value, i.e. the difference between the respectively highest and respectively lowest CTE values ​​of the samples taken from the precision component. Therefore, the CTE homogeneity does not refer to the CTE of the material of the component, but to the spatial variation of the CTE on the considered detail or the entire precision component. In order to determine the CTE homogeneity, a large number of samples are taken from different positions of the precision component and the CTE values ​​are determined for each of them in ppb / K, where 1 ppb / K=0.001×10 -6 / K. The CTE uniformity, i.e. the spatial variation of CTE, is advantageously at most 5 ppb / K, preferably at most 4 ppb / K, most preferably at most 3 ppb / K over the entire precision component. Methods for determining CTE uniformity and measures for achieving CTE uniformity are described in WO2015 / 124710 A, the disclosure of which is fully incorporated into the present application.

[0135] Thermal hysteresis

[0136] In the context of the present invention, the glass ceramic has a thermal hysteresis of <0.1 ppm at least in the temperature range from 10° C. to 35° C. and is therefore hysteresis-free (see Figures 10 to 12 ). Thus, at any temperature within the temperature interval from 10°C to 35°C, the glass-ceramic exhibits an isothermal length change of less than 0.1 ppm at a subsequent constant temperature after it has been subjected to a temperature change.

[0137] In an advantageous embodiment, this lack of hysteresis exists at least in a temperature range of 5 to 35°C, preferably at least in a temperature range of 5 to 45°C, preferably at least in a temperature range of >0°C to 45°C, preferably at least in a temperature range of -5°C to 50°C. The temperature range without hysteresis is particularly preferably wider, so that the material or component is also suitable for applications at temperatures up to at least 100°C and advantageously higher. The temperature range without hysteresis is particularly preferably wider. Preferred application temperatures are in the range of -60 to 100°C, more preferably -40°C to +80°C. A special variant of the invention relates to glass ceramics and precision components for application temperatures TA, for example in the range of 5°C to 20°C or TA of 22°C, 40°C, 60°C, 80°C and 100°C, preferably also without hysteresis at these temperatures.

[0138] The thermal hysteresis was determined for the glass ceramics and precision components according to the invention and for comparative examples on a precision dilatometer that can determine the CTE with a reproducibility of ±0.001 ppm / K and ±0.003 ppm / K absolute values ​​by temperature intervals of 1°C on samples of rod-shaped test pieces with a length of 100 mm and a diameter of 6 mm (i.e., precision component samples or glass ceramic samples) according to the method and device structure disclosed in DE 10 2015113 548 A (the disclosure of which is fully incorporated into the present application). For each sample, the temperature-dependent length change Δl / l was measured between cooling from 50°C at a cooling rate of 36 K / h to -10°C. 0 After isothermal holding at -10 °C for 5 h, the sample was heated to 50 °C at a heating rate of 36 K / h and the length change Δl / l as a function of temperature was recorded. 0 The thermal hysteresis behavior of the test piece was observed at -5°C, 0°C, 5°C, 10°C, 22°C, 35°C, and 40°C. These points represent the temperature range of -10°C to 50°C, because the hysteresis in the temperature interval decreases as the temperature increases. Therefore, samples with no hysteresis at 22°C or 35°C also do not show hysteresis in the range up to 50°C.

[0139] To determine the thermal hysteresis at 10°C, individual measured values ​​of the length change at five temperatures of 8°C, 9°C, 10°C, 11°C and 12°C are recorded, i.e. two temperature points above and below 10°C respectively, when heating and cooling the sample at a rate of 36 K / h in the range of -10°C to 50°C. The average value is formed from the difference in the measured values ​​of the heating and cooling curves at these five measuring points and is reported in the table as "Hysteresis @ 10°C" in [ppm].

[0140] To determine the thermal hysteresis at 35°C, the corresponding individual measured values ​​of the length change at five temperatures of 33°C, 34°C, 35°C, 36°C and 37°C are recorded, i.e. two temperature points above and below 35°C, respectively, when heating and cooling the sample at a rate of 36 K / h in the range of -10°C to 50°C. From the differences in the measured values ​​of the heating and cooling curves at these five measuring points, an average value is formed and recorded in the table as "Hysteresis @ 35°C" in [ppm].

[0141] The same procedure was followed for the other temperature points mentioned above.

[0142] The accompanying drawings show a glass ceramic according to the present invention ( Figures 10 to 12 ) and known glass ceramics ( Figures 2 to 9 ). For better comparability, the range of 6 ppm on the y-axis is always selected for the graphs in the figures.

[0143] Figures 2 to 8 The thermal hysteresis curves of known materials for precision components are shown. The cooling curve (dashed line) and the heating curve (dots) are each clearly spaced apart from one another, especially at lower temperatures, i.e. they run distinctly apart. At 10°C, the spacing exceeds 0.1 ppm, and according to the comparative example, the difference is up to about 1 ppm. This means that the materials and precision components made from them show considerable thermal hysteresis in the relevant temperature range of at least 10° to 35°C.

[0144] The LAS glass ceramics studied, such as Figures 2 to 5 As shown in (Comparative Examples 7, 9 and 10 in Table 2), all contain MgO and ZnO and have thermal hysteresis over a wide temperature range of 10°C to 35°C. Figure 6 and 7 The hysteresis curves of LAS glass ceramics without MgO but with ZnO (Comparative Examples 8 and 14 in Table 2) are shown. Both materials show a strongly increased thermal hysteresis below 15°C. Figure 8 The hysteresis curve of LAS glass ceramic containing no ZnO but MgO (Comparative Example 15 in Table 2) is shown. This material also shows a strongly increased thermal hysteresis below 15°C. Fig. 9 As can be seen from the graph, this known material (Comparative Example 1 in Table 2) has no thermal hysteresis, but the steep curve progression shows that it is not a zero expansion material. The average CTE here is -0.24 ppm / K.

[0145] The LAS glass ceramics and precision components according to the invention have a very low MgO and / or ZnO content or are preferably free of MgO and ZnO. Figures 10 to 12It can be seen that the heating curve and the cooling curve overlap at least in the temperature range of 10° C. to 35° C., i.e. the glass ceramic has no hysteresis. However, the material has no hysteresis not only in the range of 10° C. to 35° C., but also at least in the range of 5 to 35° C. or 5 to 45° C., preferably at least in the range of >0° C. to 45° C. Fig.11 and 12 Examples 6 and 7 in FIG. 1 also have no hysteresis at least in the temperature range of -5°C to 50°C.

[0146] Other expansion properties

[0147] Advantageous embodiments of the present invention have further advantageous expansion characteristics:

[0148] TCL values ​​are usually used to describe the expansion behavior of test pieces (glass ceramics or precision parts), where TCL stands for "total change in length". Within the scope of the present invention, TCL values ​​are specified for the temperature range 0°C and 50°C. They are derived from the standardized Δl / l of the corresponding test piece. 0 -T curve (also Δl / l in the figure) 0 -T curve) where "normalized" means that the length change is 0 ppm at 0°C. Δl / l for TCL determination 0 The -T curve is constructed using the same method as described above in connection with the CTE determination within the scope of the present invention.

[0149] The TCL value is dl / l within this temperature range. 0 Maximum value and dl / l 0 Distance between minima:

[0150] TCL(0;50℃)=|dl / l 0 max|+|dl / l 0 min|(2)

[0151] Where "dl" is the length change at the corresponding temperature, and "l 0 " indicates the length of the test piece at 0°C. When calculating, use dl / l 0 value.

[0152] Figures 16 to 19 shows the expansion curve of a known material, where dl / l 0 Maximum value and dl / l 0 The minimum value can be read off in each case for calculating the TCL value (see also below). The expansion curves show the curve profile in each case in the temperature range from 0° C. to 50° C.

[0153] However, within the scope of the present invention, the flat course of the expansion curve in the temperature range of 0° C. to 50° C. is an advantageous feature of glass ceramics and precision components (see Figures 13 to 15 ). For some advantageous variants, depending on the field of application of the component, a flat profile of the expansion curve is also desirable for other temperature ranges, in particular in the ranges of (20; 40), (20; 70) and / or (-10; 30).

[0154] As an indication of the extent to which the trend of the thermal expansion curve deviates from a simple linear trend, the parameter F is introduced as a measure of the flatness of the expansion curve of an advantageous embodiment of the invention, whereby the CTE curve can be classified:

[0155] F = TCL (0; 50 ° C) / | expansion (0; 50 ° C) | (3)

[0156] The parameter F is calculated by forming the quotient of the TCL (0; 50) value (in ppm) (see above) and the expansion difference (in ppm) between the temperature points 0°C and 50°C. Since the expansion curve determined by TCL is standardized according to regulations so that the length change at 0°C is 0 ppm, the "expansion difference between the temperature points 0°C and 50°C" corresponds to the "expansion at 50°C", as shown in the table. The expansion at 50°C is used to calculate the parameter F.

[0157] It is advantageous here if the parameter F of the respective material or component is <1.2, preferably <1.1, preferably at most 1.05. The closer the parameter F is to 1, the flatter the expansion curve runs.

[0158] exist Figures 13 to 15 It can be seen from the figure that advantageous embodiments of LAS glass ceramics have a flat profile of the expansion curve (eg F=1) in the temperature range of 0°C to 50°C and preferably in a wider temperature range of -10°C to 70°C. In contrast, Figures 16 to 20 It is shown that the known materials exhibit a significantly steeper and more curved course of the expansion curve in the temperature range considered.

[0159] Fig.13 The expansion curve of a favorable glass ceramic based on the favorable ceramicization (maximum temperature 830° C., duration 3 days) of Example 7 is shown by way of example. The section of 2.4 ppm on the y-axis is selected for display. The maximum expansion value (dl / l 0 max) is at +50℃ (dl / l 0 +0.57ppm, i.e. |0.57ppm|), minimum expansion value (dl / l 0 min) is 0 ppm. The difference in expansion between the temperature points of 0°C and 50°C corresponds to the amount of "expansion at 50°C", which is 0.57 ppm. From this, the parameter F of the material is calculated as follows: F (Example 7 in Table 1) = 0.57 ppm / 0.57 ppm = 1.

[0160] Fig.14 The favorable flat trend of the expansion curve of the other ceramicized glass ceramics in the temperature range of -10°C to 80°C in Example 7 (maximum temperature 825°C, duration 3 days) in Table 1 is also shown. This favorable expansion behavior is also shown in Fig.15 In Example 6.

[0161] Advantageous glass ceramics and precision components according to the invention therefore have, for example, a very flat expansion curve in the temperature range from 0° C. to 50° C., i.e. they not only have zero expansion in the temperature range under consideration, but also have small fluctuations in the variation of the linear expansion and thus small fluctuations in the differential CTE in this region. Fig.14 and 15 As can be seen in FIG. 1 , advantageous examples of the invention also have a flat course of their expansion curves over an even wider temperature range (here exemplarily from −10° C. to +70° C. or +80° C.). Fig. 20 The significantly steeper expansion curves of the known materials can be seen in Figure 1 for the same temperature range. The expansion behavior can also be considered in other selected temperature ranges, in particular (-10; 30), (20; 40, (20, 70), as described below.

[0162] Compared to the advantageous embodiments of glass ceramics and precision components, Figures 16 to 19 The expansion behavior of known materials and precision components made of them is shown, from which the parameter F can be calculated respectively. Figures 16 to 20 As shown, the expansion behavior of materials or precision parts is measured using the same dilatometer as Figures 13 to 15 The expansion behavior of the advantageous embodiments of the glass ceramics shown is determined under comparable conditions. In general, the known materials show a curved course of the expansion curve:

[0163] Fig.16 It shows that the commercially available titanium-doped quartz glass has the same dl / l 0 The expansion curve below, details are as follows Figures 13 to 15 As shown. It can be seen that the sum of the expansion values ​​at +50°C (dl / l 0 max is +0.73ppm, i.e. |0.73ppm|) and the expansion value at 14°C (dl / l 0 min is -0.19 ppm, i.e. |0.19 ppm|) to obtain a TCL(0;50) value of about 0.92 ppm. The expansion difference between the temperature points of 0°C and 50°C corresponds to the amount of "expansion at 50°C", which is 0.73 ppm. Thus, the parameter F of the material is calculated as follows: F(Titanium-doped SiO 2 )=0.92ppm / 0.73ppm=1.26.

[0164] Thus, LAS glass ceramics or corresponding precision parts (see Fig.17 ) is calculated as follows: F(known LAS glass ceramics) = 1.19 ppm / 0.11 ppm = 10.82.

[0165] Therefore, cordierite glass ceramics or corresponding precision parts (see Fig.18 ) is calculated as follows: F(known cordierite glass-ceramics)=2.25ppm / 0.25ppm=9.

[0166] Therefore, it is known to sinter cordierite ceramics or corresponding precision parts (see Fig.19 ) is calculated as follows: F (known sintered cordierite ceramic) = 4.2ppm / 2.71ppm = 1.55.

[0167] Glass ceramics with a flat course of expansion curves are very advantageous, because now precision components can not only be optimized for the subsequent application temperature, but also have a similarly low thermal expansion, for example, under higher and / or lower temperature loads, for example during the manufacturing process. Precision components for microlithography, EUV microlithography (also referred to as "EUV lithography" or "EUVL") and metrology are usually used under standard clean room conditions, in particular at room temperature of 22°C. The CTE can be adapted to this application temperature. However, these components are subject to various process steps, such as metal layer coating, cleaning processes, structuring processes and / or exposure processes, in which there may be temperatures that are higher or in some cases lower than the aforementioned temperatures that are subsequently applied in the clean room. Advantageous glass ceramics and precision components made from them are therefore very advantageous, which have a parameter F of <1.2 and therefore have an optimized zero expansion not only at the application temperature but also, if necessary, at higher and / or lower temperatures during production. If the precision component or glass ceramic is used in EUV lithography, i.e. if the precision component is, for example, an EUVL mirror or an EUVL mask blank or a corresponding substrate, properties such as the absence of hysteresis and the parameter F<1.2 are particularly advantageous, since in EUV lithography, in particular the mirror or mask is heated very inhomogeneously in the point or beam direction by the use of rays of high-energy radiation. For such conditions of use, it is advantageous if the precision component or glass ceramic has a CTE-T curve with a low slope in the temperature range around the application temperature (see below).

[0168] Advantageous glass ceramics and precision components are even better optimized for a subsequent application temperature of 20 or 22°C and are distinguished by a relative length change (dl / l) in the temperature range of 20°C to 30°C. 0)≤|0.10|ppm, preferably ≤|0.09|ppm, particularly preferably ≤|0.08|ppm, particularly preferably ≤|0.07|ppm and / or having a relative length change (dl / l) in the temperature range of 20°C to 35°C 0 )≤|0.17|ppm, preferably ≤|0.15|ppm, particularly preferably ≤|0.13|ppm, particularly preferably ≤|0.11|ppm. Alternatively or additionally, the optimized glass ceramic and precision component are distinguished in that they have a relative length change (dl / l) in the temperature range of 20°C to 40°C. 0 )≤|0.30|ppm, preferably ≤|0.25|ppm, particularly preferably ≤|0.20|ppm, particularly preferably ≤|0.15|ppm. The characteristics based on the relative length change in different temperature intervals can be preferably obtained from Figures 13 to 19 dl / l 0 If the relative length change (dl / l 0 ), the data naturally refers to the corresponding value.

[0169] Zero-expansion, hysteresis-free materials with such favorable expansion behavior are particularly suitable for use as substrates for EUVL mirrors or EUVL mirrors which are heated to different degrees in the light and shadow regions during operation, for example due to corresponding exposure masks. Due to the above-mentioned smaller relative length changes, EUVL mirrors formed from the favorable glass ceramics have lower local gradients (local gradients or local slopes) in the mirror topography than EUVL mirrors made of known materials. The same applies to EUVL mask blanks or EUVL masks or EUVL photomasks.

[0170] In particular, in the case of glass ceramics which exhibit a very flat expansion curve in the temperature range under consideration, which is close to 0 ppm or fluctuates around 0 ppm, which is generally a favorable expansion behavior, it may be advantageous to introduce a further measure of the flatness of the expansion curve as an alternative or in addition to the parameter F, wherein the expansion curve is not in the temperature range (0; 50), but in another temperature interval (Ti), preferably in the temperature range under consideration (20; 40), (20; 70) and / or (-10; 30). This allows for a better classification of the expansion behavior in relation to the subsequent field of application.

[0171] The alternative parameter fT.i. is expressed in (ppm / K) and is defined as:

[0172] f T.i. =TCL (T.i.) / Temperature interval width (Ti) (4)

[0173] where Ti describes the temperature interval considered.

[0174] TCL (T.i.) The value is the maximum dl / l in the respectively considered temperature range (Ti) 0 Value and minimum dl / l 0 The distance between the values, where TCL (T.i.) The determined expansion curves are standardized according to regulations so that the length change is 0 ppm at 0° C. This means, for example:

[0175] TCL (20;40℃) =|dl / l 0 max|+|dl / l 0 min| (5)

[0176] Where "dl" is the length change at the corresponding temperature, and "l 0 " indicates the length of the test piece at 0°C. When calculating, use dl / l 0 value.

[0177] Substitution parameter f T.i. According to formula (4), by taking TCL (T.i.) The value [in ppm] (see above) is calculated as the quotient of the temperature interval (Ti) in which the expansion difference is taken into account (in K). The width of the temperature interval between 20° C. and 40° C. taken into account is 20 K. If, on the other hand, the course of the expansion curve is taken into account in the interval Ti=(20; 70) or (-10; 30), the divisor of formula (4) is 50 K or 40 K.

[0178] In an advantageous embodiment, the glass ceramic has the substitution parameter f (20;40) <0.024ppm / K and / or alternative parameter f (20;70) <0.039ppm / K and or alternative parameter f (-10;30) <0.015ppm / K.

[0179] Glass ceramics with a very flat course of the expansion curve are very advantageous, since now the precision component can be optimized not only for the subsequent application temperature, but also, for example, for expected higher and / or lower temperature loads. T.i. Suitable for specifying suitable materials according to the specifications required for a particular component application and providing the corresponding precision components. Special precision components and their applications are described below and are included here.

[0180] According to an advantageous embodiment of the glass ceramic or of a component made therefrom, it may be advantageous to replace the parameter f (20;40)<0.024 ppm / K, preferably <0.020 ppm / K, preferably <0.015 ppm / K. Hysteresis-free, zero-expansion components with such an expansion behavior in the temperature range (20; 40°C) can be used particularly well as precision components for microlithography and EUV microlithography at room temperature. Examples of such advantageous glass ceramics can be found in Fig.14 and 15 Seen in.

[0181] According to an advantageous embodiment of the glass ceramic or of a component made therefrom, it may be advantageous to replace the parameter f (20;70) <0.039ppm / K, preferably <0.035ppm / K, preferably <0.030ppm / K, preferably <0.025ppm / K, preferably <0.020ppm / K. Hysteresis-free, zero-expansion components with such an expansion behavior in the temperature range (20; 70°C) can also be used particularly well as precision components for microlithography and EUV microlithography. It is particularly advantageous that the components have a similarly low thermal expansion even at higher temperature loads, which may occur, for example, during the manufacture of the precision components, but which may also occur locally or over large areas during operation. The temperature loads occurring in EUVL precision components have been described above in more detail in conjunction with parameter F, to which reference is made here to avoid repetition. An example of such an advantageous glass ceramic is Fig.14 Shown in.

[0182] According to an advantageous embodiment of the glass ceramic or of a component made therefrom, it may be advantageous to replace the parameter f (-10;30) <0.015 ppm / K, preferably <0.013 ppm / K, preferably <0.011 ppm / K. Hysteresis-free, zero-expansion components with such an expansion behavior in the temperature range (-10; 30°C) can be used particularly well as precision components, in particular as mirror substrates for applications in which temperatures below room temperature also occur, for example as mirror substrates in astronomy or for Earth observation from space. The corresponding components are described in more detail below. An example of such an advantageous glass ceramic is Fig.15 Shown in.

[0183] Particularly advantageous embodiments of the glass ceramic or of a component made therefrom have an expansion curve for which at least two selectable parameters f (T.i.) Applicable.

[0184] A particularly advantageous embodiment of the glass ceramic or in particular the component made of glass ceramic has an expansion curve for which the parameter F and the at least one alternative parameter f (T.i.) is applicable.

[0185] Figures 21 to 25It is shown that advantageous embodiments of LAS glass ceramics and precision components have a CTE “plateau.” Glass ceramics with a plateau, ie with an optimized zero expansion over a wide temperature range, offer the same advantages associated with the flat profile of the expansion curve and parameter F already described above.

[0186] Advantageously, the differential CTE has a plateau close to 0 ppm / K, i.e., has a temperature interval T of at least 40 K, preferably at least 50 K. P The differential CTE in is less than 0±0.025ppm / K. The temperature range of the CTE platform is denoted by T P Advantageously, the differential CTE is in a temperature interval T with a width of at least 40K. P The concentration can be less than 0±0.015ppm / K.

[0187] Therefore, the CTE platform is understood to be a region extending on a segment of the CTE-T curve, wherein the value of the differential CTE does not exceed 0±0.025 ppm / K, preferably 0±0.015 ppm / K, more preferably 0±0.010 ppm / K, more preferably 0±0.005 ppm / K, i.e., the CTE is close to 0 ppb / K.

[0188] Advantageously, the differential CTE may be less than 0±0.015 ppm / K, i.e. 0±15 ppb / K, in a temperature interval TP having a width of at least 40 K. In a preferred embodiment, a CTE plateau of 0±0.01 ppm / K, i.e. 0±10 ppb / K, may be formed over a temperature interval of at least 50 K.

[0189] It may be advantageous if the temperature interval T P In the range of -10 to +100°C, preferably 0 to 80°C.

[0190] The position of the CTE plateau of the glass ceramic is preferably adapted to the application temperature T of the precision part. A Preferably, the application temperature T A In the temperature range of -60°C to +100°C, more preferably -40°C to +80°C. A special variant of the invention relates to the use of a temperature T A The CTE platform, i.e. the curve region with a small differential CTE deviation in the temperature interval Tp, can also be in the temperature ranges of [-10; 100], [0; 80], [0; 30°C], [10; 40°C], [20; 50°C], [30; 60°C], [40; 70°C] and / or [50; 80°C].

[0191] According to Example 6 in Table 1, Fig.21It is shown that the CTE of the glass ceramic is 0±0.010 ppm / K in the entire temperature range of -10°C to 90°C, i.e., has a 10 ppb platform. Fig. 22 ) can be seen from the details of the glass ceramic that has a CTE of 0±0.005 ppm / K in the temperature range of -5°C to 32°C. This glass ceramic meets the average CTE (19; 25) requirements for EUVL substrates and blanks specified in the SEMIP37-1109 standard.

[0192] Fig.23 It is shown that Example 7 in Table 1 is ceramicized at a maximum temperature of 825°C for 3 days, and the glass ceramic has a CTE of 0±0.010 ppm / K from 12°C, that is, a 10 ppb platform, and its width is greater than 40K. Fig.24 As shown, the exemplary range between 16° C. and 40° C. even has a CTE of 0±0.005 ppm / K, thus also meeting the requirements for average CTE (19; 25) specified in the SEMIP37-1109 standard for EUVL substrates and blanks.

[0193] Fig.25 Example 9 of Table 1 is shown, which is ceramicized at a temperature of up to 830° C. for 3 days, and the glass ceramic has a CTE of 0±0.010 ppm / K in the range shown between −5° C. and 45° C., ie, has a 10 ppb plateau.

[0194] According to an advantageous embodiment of the invention, the CTE-T curve of the glass ceramic or precision component has at least one curve section with a low slope, in particular up to 0±2.5 ppb / K, in a temperature interval with a width of at least 30 K, preferably at least 40 K, more preferably at least 50 K. 2 , Advantageously up to 0±2ppb / K 2 , Advantageously up to 0±1.5ppb / K 2 , preferably up to 0±1ppb / K 2 , preferably up to 0±0.8ppb / K 2 Depending on the specific variant, even up to 0 ± 0.5 ppb / K 2 The slope of .

[0195] The temperature range with a smaller slope is preferably adapted to the application temperature T of precision components. A Preferably, the application temperature T A In the temperature range of -60°C to +100°C, more preferably -40°C to +80°C. A special variant of the invention relates to the use of a temperature T AGlass ceramics and precision parts at 0°C, 5°C, 10°C, 22°C, 40°C, 60°C, 80°C and 100°C. The low slope temperature interval can also be in the temperature range of [-10; 100], [0; 80], [0; 30°C], [10; 40°C], [20; 50°C], [30; 60°C], [40; 70°C] and / or [50; 80°C].

[0196] Fig.26 The slope of the CTE-T curve of an advantageous glass ceramic or precision component based on the composition of Example 6 from Table 1 in the temperature range of 0°C to 45°C is shown. The CTE slope is less than 0±1 ppb / K over the entire temperature range. 2 And in a range of at least 30K (from about 12℃) it is even lower than 0±0.5ppb / K 2 .

[0197] exist Fig. 27 As can be seen from the table 1, the CTE slope of the advantageous glass ceramics and precision parts according to Example 7 is less than 0±1.0 ppb / K over the entire temperature range from 0°C to 45°C with a width of at least 45K. 2 And in a range of at least 40K (in the illustrated range between 0 and 42°C), it is even lower than 0±0.5ppb / K. 2 .

[0198] Glass ceramics and precision components with such expansion properties are particularly suitable for EUV lithography applications (e.g. as mirrors or substrates for mirrors or masks or mask blanks), since in this area the requirements on materials for optical components and precision components are increasing with regard to having very low thermal expansion, a zero crossing of the CTE-T curve close to the application temperature and in particular a low slope of the CTE-T curve. Within the scope of the invention, advantageous embodiments of the glass ceramic or precision component have a very flat CTE curve, wherein the curve shows a zero crossing and a very low CTE slope and, if necessary, a very flat plateau.

[0199] Low slope features may exist with or without the formation of a favorable CTE plateau.

[0200] Fig.28 and 29 It is shown how the expansion curve can be adapted to different application temperatures by varying the ceramicizing temperature and / or the ceramicizing time.

[0201] According to Example 6, Fig.28It can be seen from Example 6 that by selecting the maximum ceramizing temperature for the initial green glass, the resulting expansion curve of the glass ceramic can be specifically influenced. The dotted curve represents the expansion curve of a glass ceramic whose base green glass was ceramized at a maximum temperature of 810°C for 2.5 days, while the dashed-dotted curve represents the expansion curve of a glass ceramic whose base green glass was ceramized at 820°C for 2.5 days. In addition, Fig.28 It is shown by way of example that the glass ceramic according to the present invention can be re-ceramicized, which means that, by carrying out a new heat treatment to the already ceramicized material, the expansion curve of the glass ceramic can be fine-tuned in a targeted manner. In this case, the glass ceramic material that was ceramicized for 2.5 days at a maximum of 810°C was re-ceramicized for 1.25 days at 810°C again, i.e. with a shortened holding time. The effect of this re-ceramicization is shown in the form of a dotted expansion curve. Comparing the expansion curves, it can be seen that the expansion curves before and after re-ceramicization and therefore the average CTE (0; 50) are different. However, the XRD analysis of the sample before and after ceramicization shows that, within the range of measurement accuracy, the results of the average crystal size and the crystalline phase ratio are respectively the same.

[0202] Fig.29 The adjustability of the expansion curve at different maximum ceramizing temperatures during ceramizing of the same initial green glass is shown for Example 7. The dashed line shows: ceramizing at a maximum of 830° C. for 3 days; the dots show: ceramizing at a maximum of 825° C. for 3 days.

[0203] As an alternative to increasing the ceramicizing temperature, the ceramicizing time can also be extended accordingly.

[0204] Advantageous glass ceramics and precision parts also have good intrinsic quality. It is preferably per 100 cm 3 A maximum of 5 inclusions, preferably per 100 cm 3 Maximum 3 inclusions, preferably per 100cm 3 Maximum 1 inclusion. Inclusions are understood according to the invention to mean gas bubbles and crystallites with a diameter greater than 0.3 mm.

[0205] According to one embodiment of the invention, a plurality of spherical plates having a diameter or edge length of at most 800 mm and a thickness of at most 100 mm are provided. 3 Precision components each having up to 5, preferably up to 3, more preferably up to 1 inclusion with a diameter greater than 0.03 mm.

[0206] In addition to the number of inclusions, the maximum diameter of the detected inclusions can also serve as a measure of the internal quality. The maximum diameter of a single inclusion in the total volume of a precision component with a diameter of less than 500 mm is preferably up to 0.6 mm, and in volumes critical to the application, such as near the surface, preferably up to 0.4 mm. The maximum diameter of a single inclusion in a glass-ceramic component with a diameter of 500 mm to less than 2 m is preferably up to 3 mm, and in volumes critical to the application, such as near the surface, preferably up to 1 mm.

[0207] The invention also relates to the use of the glass ceramic according to the invention in precision components. For example, the glass ceramic can form a substrate for a precision component.

[0208] Furthermore, the invention relates to the use of the LAS glass ceramic according to the invention in precision components, in particular for use in metrology, spectroscopy, measuring technology, lithography, astronomy or Earth observation from space, for example as a mirror or mirror carrier for a segmented or integral astronomical telescope, or also as a substrate for a lightweight or ultralight mirror, for example for a space-based telescope, or as a high-precision structural component for distance measurement, for example in space-based optics or for Earth observation, as a precision component, for example a standard for precise measuring technology, a precision measuring rod, a reference plate in an interferometer, as a mechanical precision component, for example for a ring laser gyroscope, a helical spring for watchmaking, for example as a mirror and prism in LCD lithography, and for example as a mask holder, a wafer stage, a reference plate, a reference frame and a grid plate in microlithography and EUV (extreme ultraviolet) microlithography, and furthermore as a mirror or a mirror substrate and / or a photomask substrate or a photomask blank or a photomask mask blank in EUV microlithography.

[0209] Using the glass ceramics according to the invention, precision components of different sizes can be produced:

[0210] One embodiment relates to precision components with relatively small dimensions, in particular with an edge length (width and / or depth) of at least 100 mm and / or at most 1500 mm in an angular (rectangular) shape or with a diameter of at least 100 mm and / or at most 1500 mm in a rounded surface and / or a thickness of less than 50 mm, preferably less than 10 mm and / or at least 1 mm, more preferably at least 2 mm. Such precision components can be used, for example, for microlithography and EUV lithography.

[0211] Another embodiment relates to precision components with very small dimensions, in particular with an edge length (width and / or depth) or a diameter and / or thickness of a few mm (e.g. up to 20 mm or up to 10 mm or up to 5 mm or up to 2 mm or up to 1 mm) to a few tenths of a mm (e.g. up to 0.7 mm or up to 0.5 mm). These precision components can be, for example, spacers in interferometers or components of ultra-stable clocks for quantum technology.

[0212] However, it is also possible to manufacture very large precision parts. One embodiment of the invention therefore relates to parts with a large volume. For this purpose, in the sense of the present application it is understood to be a part having a mass of at least 300 kg, preferably at least 400 kg, preferably at least 500 kg, preferably at least 1 t, more preferably at least 2 t, at least 5 t according to a variant of the invention, or a part having an edge length (width and / or depth) of at least 0.5 m, more preferably at least 1 m and a thickness (height) of at least 50 mm, preferably at least 100 mm in an angular (rectangular) shape, or a part having a diameter of at least 0.5 m, more preferably at least 1 m, more preferably at least 1.5 m and / or a thickness (height) of at least 50 mm, preferably at least 100 mm in a circular shape. In a specific embodiment of the invention, the parts may also be larger, for example having a diameter of at least 3 m or at least 4 m or more. According to a variant, the invention also relates to a rectangular part, wherein preferably at least one surface has a mass of at least 1 m 2 , preferably at least 1.2m 2 , more preferably at least 1.4 m 2 Typically, large volume components are manufactured whose base area is much larger than their height. However, they can also be large volume components with an approximately cubic or spherical shape.

[0213] The precision component can be, for example, an optical component and be a so-called normal incidence mirror, i.e. a mirror which operates at nearly normal incidence, or a so-called grazing incidence mirror, i.e. a mirror which operates at grazing incidence. In addition to the substrate, such a mirror also comprises a coating which reflects the incident radiation. In particular in the case of mirrors for X-rays, the reflective coating is, for example, a multilayer system or a multilayer with a plurality of layers having a high reflectivity in the non-grazing incidence X-ray range. The multilayer system of such a normal incidence mirror preferably comprises 40 to 200 layer pairs, which consist of alternating layers, for example one of the material pairs Mo / Si, Mo / Bi, Ru / Si and / or MoRu / Be.

[0214] In particular, the optical element according to the invention can be an X-ray optical element, i.e. an optical element used in combination with X-rays, in particular soft X-rays or EUV rays, in particular a reticle mask or photomask operating in reflection, in particular for EUV microlithography. It can advantageously be a mask blank. Furthermore, the precision component can advantageously be used as a mirror for EUV lithography or as a substrate for a mirror for EUV lithography.

[0215] Furthermore, the precision components according to the invention can be components for astronomical applications, in particular mirrors. Here, these components can be used for astronomical applications on the ground and in space. High-precision structural components for distance measurement, for example in space, are another advantageous field of application.

[0216] The precision component according to the invention may involve a lightweight structure. The component of the invention may also include a lightweight structure. This means that hollow spaces are provided in certain areas of the component to reduce weight. Preferably, the weight of the component processed by lightweight processing is reduced by at least 80%, more preferably by at least 90%, compared to the unprocessed component.

[0217] The subject of the present invention is also a precision component, which comprises the LAS glass ceramic according to the present invention. This has been described in detail above in conjunction with the glass ceramic and its use in precision components. The entire disclosure is contained in the description of the precision component.

[0218] It goes without saying that the features of the invention mentioned above and still to be explained below can be used not only in the respectively specified combination but also in other combinations, without departing from the scope of the present invention.

[0219] Example

[0220] Tables 1 and 2 show the compositions of examples and comparative examples of the glass ceramics according to the present invention and their properties.

[0221] The compositions mentioned in Table 1 are melted from commercial raw materials such as oxides, carbonates and nitrates in conventional manufacturing processes, where different fining agents or combinations of fining agents are used. 2 O 3 As a fining agent, significantly reduce or use As 2 O 3 In Example 7, SnO 2 and sulfate clarification, 0.19Mol% SO 3 Take Na 2 SO 4 was added to the synthesis, equivalent to 0.22Mol% SO 4 2-In X-ray fluorescence analysis of green glass or glass ceramics, SO 3 The content is below the detection limit <0.02 wt %. The green glass manufactured according to Table 1 was first ceramicized for a specified duration at a respectively specified maximum temperature. Samples were also established for Examples 6 and 7, which were ceramicized with other ceramicizing parameters (particularly different maximum temperatures), as explained above in conjunction with the accompanying drawings.

[0222] For example, WO 2015 / 124710 A1 describes the production of glass ceramics for precision components, in particular large precision components.

[0223] Table 1 shows 15 examples (Bsp.) of the present invention, which have no hysteresis and zero expansion at least in the temperature range of 10°C to 35°C. Examples 1, 8 and 13 only show thermal hysteresis starting from about 5°C, and Examples 2 and 9 only start from about -5°C. Examples 3, 5, 6 and 7 have no hysteresis in the entire temperature range of -5°C to 45°C. In addition, the parameter F<1.2, that is, the course of the expansion curve in the temperature range from 0°C to 50°C is advantageously flat in all examples. In addition, the examples have a processing temperature of ≤1330°C, so that glass ceramics can be manufactured with high uniformity in large-scale production facilities. The processing temperatures specified in Tables 1 and 2 are derived according to DIN ISO 7884-1 (2014, source: Schott Techn. Glass-Katalog).

[0224] In Example 7, after 2.5 days of ceramicization at a maximum temperature of 810°C, the average CTE in further temperature intervals was determined and the results were as follows: CTE (20; 300°C): +0.13ppm / K, CTE (20; 500°C): +0.34ppm / K, CTE (20; 700°C): +0.59ppm / K.

[0225] For Examples 6 and 7, the average CTE was determined in the temperature range of 19° C. to 25° C., with the CTE (19; 25) of Example 6 being 0.77 ppb / K and the CTE (19; 25) of Example 7 being 0.37 ppb / K.

[0226] Example 10: SnO 2 In addition, it also contains nitrates as oxidants, namely the components BaO and Na 2 O is used as a nitrate raw material to adjust the oxidizability of the melt.

[0227] Example 15: SnO 2 Clarify. SnO 2 Also used as a nucleating agent. Another nucleating agent is ZrO 2 .

[0228] Table 2 shows the comparative examples (Vgl.Bsp). Comparative Examples 1, 2, 5, and 6 have neither MgO nor ZnO, but have an average CTE (0; 50) greater than 0 ± 0.1 × 10 -6 / K, ie these comparative examples are not zero expansion. Furthermore, comparative examples 1 and 2 have a processing temperature of >1330° C. These materials are very viscous, so that it is not possible to produce parts with a high degree of homogeneity in large-scale production facilities.

[0229] Comparative Examples 7 to 16 all contain MgO and / or ZnO, and most of them are zero expansion. However, these comparative examples show thermal hysteresis significantly greater than 0.1 ppm at least in the temperature range from 10°C to 35°C. At room temperature, i.e., 22°C, this group of comparative examples exhibits thermal hysteresis, with the exception of Comparative Examples 14 and 16. Comparative Example 9 also has an unfavorably steep expansion curve in the temperature range of 0°C to 50°C, although it is zero expansion, which can be seen from the high value of parameter F.

[0230] In the tables below, if there is a blank field in the composition information, it means that the component(s) are not intentionally added or not included.

[0231] Table 3 shows the calculation alternative parameters f for different temperature intervals of some advantageous examples and comparative examples of the present invention. (T.i.) , which indicates that the expansion curves of the examples have flatter curves than those of the comparative examples in the specified temperature range.

[0232] It is clear to the skilled person that, depending on the application temperature of the glass ceramic or the precision component comprising the glass ceramic, a glass ceramic with the desired properties is selected, in particular with regard to thermal hysteresis and / or average CTE. Table 1: Composition, ceramization and properties (Mol %)

[0233] Example number (example) 1 2 3 4 5 6 7 <![CDATA[Li 2 The]]> 8.9 8.35 8.9 8.6 9.1 9.15 9.1 <![CDATA[Na 2 The]]> 1.1 0.45 0.7 0.6 0.6 0.65 <![CDATA[K 2 The]]> 1.0 1.65 0.9 0.85 0.9 MgO ZnO 0.21 CaO 2.5 1.1 1.25 0.9 0.9 1.05 BaO 0.85 1.05 0.5 0.5 0.55 SrO 0.6 0.8 <![CDATA[Al 2 THE 3 ]]> 17.2 17.4 16.95 16.35 18.1 18.1 18.05 <![CDATA[SiO 2 ]]> 64.35 66.15 67.2 67.95 63.8 63.8 63.7 <![CDATA[P 2 THE 5 ]]> 2.9 0.8 1.5 2.65 2.65 2.7 <![CDATA[TiO 2 ]]> 2.1 2.0 2.0 2.05 2.05 2.0 2.05 <![CDATA[ZrO 2 ]]> 1.05 1.0 1.0 1.0 1.0 1.05 1.05 <![CDATA[SnO 2 ]]> 0.2 0.2 0.2 Cl 0.2 <![CDATA[Sb 2 THE 3 ]]> 0.2 0.25 0.2 0.2 0.2 0.2 <![CDATA[As 2 THE 3 ]]> sum 100.0 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[SiO 2 +(5xLi 2 O)]]> 108.85 107.90 111.70 110.95 109.30 109.55 109.20 MgO+ZnO 0.21 <![CDATA[ΣR 2 O(R=Na,K,Cs,Rb)]]> 1.1 1.45 2.35 1.5 1.45 1.55 ΣRO(R=Ca,Ba,Sr) 3.1 2.75 2.30 1.4 1.4 1.60 Va[℃] 1258 1312 Ceramic temperature[℃] 800 790 815 800 820 820 825 Ceramicization duration [days] 2.5 2.5 2.5 2.5 2.5 2.5 3 Crystalline phase [Vol. %] 64 52 53 52 57 58 58 Crystal size [nm] 45 47 46 45 47 49 49 Average CTE (0; +50℃) [ppm / K] -0.08 0.02 0.10 0.07 -0.04 0.00 -0.002 TCL(0;+50℃) 3.88 1.18 4.14 3.54 2.19 0.1 0.08 |Expansion at 50°C| 3.78 1.18 4.14 3.54 2.19 0.1 0.08 Parameter F 1.03 1.00 1.00 1.00 1.00 1.00 1.00 Hysteresis@45℃[ppm] <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@35℃[ppm] <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@30℃[ppm] <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@22℃[ppm] <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@10℃[ppm] <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@+5℃[ppm] 0.12 <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@0℃[ppm] 0.2 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@-5℃[ppm] 0.3 0.15 <0.1 <0.1 <0.1 <0.1 Ceramic temperature[℃] 800 780 830 800 820 820 830 Ceramicization duration [days] 2.5 2.5 2.5 2.5 2.5 2.5 2.5 Average CTE (-30; +70℃) [ppm / K] -0.08 -0.05 0.08 0.05 -0.06 -0.01 -0.04 Average CTE (-40; +80℃) [ppm / K] -0.10 -0.05 0.08 nb -0.07 -0.02 -0.05 Table 1 (continued): Composition, ceramization and properties (Mol%)

[0234] Example number (example) 8 9 10 11 12 13 14 <![CDATA[Li 2 The]]> 9.2 8.95 8.85 8.9 8.1 9.35 9.2 <![CDATA[Na 2 The]]> 0.6 0.4 0.55 0.4 0.7 0.45 <![CDATA[K 2 The]]> 0.8 0.9 0.8 1.0 0.25 0.6 MgO 0.17 0.35 ZnO 0.13 0.15 CaO 2.5 1.0 1.3 0.9 2.3 1.25 0.8 BaO 0.5 0.85 0.45 1.1 0.8 SrO 0.7 <![CDATA[Al 2 THE 3 ]]> 18.7 18.1 18.05 17.9 15.5 16.8 16.8 <![CDATA[SiO 2 ]]> 62.45 63.7 62.3 63.8 68.1 64.45 67.3 <![CDATA[P 2 THE 5 ]]> 3.1 2.8 4.0 2.9 1.5 3.3 <![CDATA[TiO 2 ]]> 2.0 2.0 2.0 2.0 1.9 3.85 <![CDATA[ZrO 2 ]]> 1.05 1.05 1.05 1.05 1.0 2.55 <![CDATA[SnO 2 ]]> 0.2 0.2 0.3 Cl 0.1 <![CDATA[Sb 2 THE 3 ]]> 0.25 0.2 0.25 0.2 <![CDATA[As 2 THE 3 ]]> 0.025 sum 100.0 100.0 100.0 100.0 100.0 100.0 100.0 <![CDATA[SiO 2 +(5xLi 2 O)]]> 108.45 108.45 106.55 108.30 108.60 111.20 113.30 MgO+ZnO 0.30 0.50 <![CDATA[ΣR 2 O(R=Na,K,Cs,Rb)]]> 1.4 1.3 1.35 1.4 0.95 1.05 ΣRO(R=Ca,Ba,Sr) 3.2 1.5 2.15 1.35 2.3 2.35 1.6 Va[℃] Ceramic temperature[℃] 830 830 800 830 780 800 815 Ceramicization duration [days] 3.75 2.5 2.5 2.5 2.5 2.5 2.5 Crystalline phase [Vol. %] 67 57 57 60 52 64 Crystal size [nm] 39 50 51 49 33 33 Average CTE (0; +50℃) [ppm / K] 0.04 -0.008 0.05 0.06 0.06 0.02 -0.09 TCL(0;+50℃) 4.64 0.4 2.61 3.2 3.19 1.02 4.55 |Expansion at 50°C| 4.16 0.4 2.61 3.2 3.19 1.02 4.55 Parameter F 1.12 1.00 1.00 1.00 1.00 1.00 1.00 Hysteresis@45℃[ppm] <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@35℃[ppm] <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@30℃[ppm] <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@22℃[ppm] <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@10℃[ppm] <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@+5℃[ppm] 0.16 <0.1 <0.1 <0.1 <0.1 0.13 <0.1 Hysteresis@0℃[ppm] 0.26 <0.1 <0.1 0.14 0.1 0.22 Hysteresis@-5℃[ppm] 0.4 0.11 0.11 0.205 0.17 0.27 Ceramic temperature[℃] 830 830 830 830 780 815 Ceramicization duration [days] 3.75 2.5 2.5 2.5 2.5 2.5 Average CTE (-30; +70℃) [ppm / K] 0.18 0.01 0.05 0.05 0.05 -0.03 Average CTE (-40; +80℃) [ppm / K] 0.18 0.00 0.04 0.04 0.04 -0.01 Table 1 (continued): Composition, ceramization and properties (Mol%)

[0235] Example number (example) 15 <![CDATA[Li 2 The]]> 9.0 <![CDATA[Na 2 The]]> 0.65 <![CDATA[K 2 The]]> 0.7 MgO ZnO CaO 1.0 BaO 1.55 SrO <![CDATA[Al 2 THE 3 ]]> 18.1 <![CDATA[SiO 2 ]]> 64.65 <![CDATA[P 2 THE 5 ]]> 2.15 <![CDATA[TiO 2 ]]> <![CDATA[ZrO 2 ]]> 1.6 <![CDATA[SnO 2 ]]> 0.6 Cl <![CDATA[Sb 2 THE 3 ]]> <![CDATA[As 2 THE 3 ]]> sum 100.0 <![CDATA[SiO 2 +(5xLi 2 O)]]> 109.65 MgO+ZnO <![CDATA[ΣR 2 O(R=Na,K,Cs,Rb)]]> 1.35 ΣRO(R=Ca,Ba,Sr) 2.55 Va[℃] Ceramic temperature[℃] 840 Ceramicization duration [days] 2.5 Crystalline phase [Vol. %] 52 Crystal size [nm] 61 Average CTE (0; +50℃) [ppm / K] -0.10 TCL(0;+50℃) 5.04 |Expansion at 50°C| 5.04 Parameter F 1.00 Hysteresis@45℃[ppm] <0.1 Hysteresis@35℃[ppm] <0.1 Hysteresis@30℃[ppm] <0.1 Hysteresis@22℃[ppm] <0.1 Hysteresis@10℃[ppm] <0.1 Hysteresis@+5℃[ppm] <0.1 Hysteresis@0℃[ppm] 0.13 Hysteresis@-5℃[ppm] 0.18 Ceramic temperature[℃] Ceramicization duration [days] Average CTE (-30; +70℃) [ppm / K] Average CTE (-40; +80℃) [ppm / K] Table 2: Composition, ceramicization and properties (Mol%)

[0236] Comparative Example No. (Comparative Example) 1 2 5 6 <![CDATA[Li 2 The]]> 8.1 9.15 9.45 9.5 <![CDATA[Na 2 The]]> 0.4 0.4 0.2 0.1 <![CDATA[K 2 The]]> 0.15 0.2 0.7 0.55 MgO ZnO CaO 4.15 2.2 0.4 BaO 0.6 1.75 SrO <![CDATA[Al 2 THE 3 ]]> 12.45 14.2 16.75 16.6 <![CDATA[SiO 2 ]]> 72.3 71.7 64.15 65.55 <![CDATA[P 2 THE 5 ]]> 0.62 3.3 2.2 <![CDATA[TiO 2 ]]> 1.3 1.75 2.05 2.1 <![CDATA[ZrO 2 ]]> 1.0 1.2 1.0 1.05 <![CDATA[As 2 THE 3 ]]> 0.15 0.15 0.2 0.2 sum 100.0 100.0 100.0 100.0 <![CDATA[SiO 2 +(5xLi 2 O)]]> MgO+ZnO <![CDATA[ΣR 2 O(R=Na.K.Cs.Rb)]]> 0.55 0.6 0.9 0.65 ΣRO(R=Ca.Ba.Sr) 4.15 0.6 2.2 2.15 Va[℃] 1345 1340 Ceramic temperature[℃] 760 800 800 Ceramicization duration [days] 10 2.5 2.5 Crystalline phase [Vol. %] 60 66 58 Crystal size [nm] 63 45 47 Average CTE (0; +50℃) [ppm / K] -0.25 -0.27 -0.46 TCL(0;+50℃) |Expansion at 50°C| Parameter F Hysteresis@45℃[ppm] Hysteresis@35℃[ppm] Hysteresis@30℃[ppm] Hysteresis@22℃[ppm] <0.1 Hysteresis@10℃[ppm] <0.1 Hysteresis@+5℃[ppm] <0.1 Hysteresis@0℃[ppm] 0.13 Hysteresis@-5℃[ppm] 0.24 Ceramic temperature[℃] Ceramicization duration [days] Average CTE (-30; +70℃) [ppm / K] Average CTE (-40; +80℃) [ppm / K] Table 2 (continued): Composition, ceramization and properties (Mol%)

[0237] Comparative Example No. (Comparative Example) 7 8 9 10 11 12 <![CDATA[Li 2 The]]> 8.5 7.78 9.32 9.2 9.4 9.0 <![CDATA[Na 2 The]]> 0.1 0.8 0.1 0.2 0.1 <![CDATA[K 2 The]]> 0.5 MgO 1.8 1.2 1.6 1.2 1.6 ZnO 1.3 1.8 0.4 0.6 0.6 0.4 CaO 2.42 1.0 1.2 1.0 1.3 BaO 1.07 0.36 0.4 0.3 0.5 SrO <![CDATA[Al 2 THE 3 ]]> 16.9 15.39 19.11 16.2 19.0 16.4 <![CDATA[SiO 2 ]]> 64.3 65.42 61.4 63.3 61.4 63.9 <![CDATA[P 2 THE 5 ]]> 3.4 2.47 3.97 3.8 3.9 3.5 <![CDATA[TiO 2 ]]> 1.9 1.67 1.92 2.2 1.9 2.1 <![CDATA[ZrO 2 ]]> 1.1 0.92 1.07 1.1 1.1 1.2 <![CDATA[As 2 THE 3 ]]> 0.2 0.26 0.25 0.2 0.2 0.1 sum 100.0 100.0 100.0 100.0 100.0 100.1 <![CDATA[SiO 2 +(5xLi 2 O)]]> MgO+ZnO 3.1 1.8 1.6 2.2 1.8 2.0 <![CDATA[ΣR 2 O(R=Na,K,Cs,Rb)]]> 0.6 0.8 0.1 0.2 0.1 ΣRO(R=Ca,Ba,Sr) 3.49 1.36 1.6 1.3 1.8 Va[℃] Ceramic temperature[℃] 810 760 810 760 Ceramicization duration [days] 10 10 5 10 Crystalline phase [Vol. %] 76 Crystal size [nm] 72 Average CTE (0; +50℃) [ppm / K] 0.03 0.02 0.002 -0.15 0.03 -0.05 TCL(0;+50℃) 1.19 3.68 1.32 0.35 |Expansion at 50°C| 0.11 3.68 1.28 0.35 Parameter F 10.82 1.00 1.03 1.00 Hysteresis@45℃[ppm] 0.11 <0.1 <0.1 <0.1 <0.1 <0.1 Hysteresis@35℃[ppm] 0.14 <0.1 0.12 <0.1 <0.1 <0.1 Hysteresis@30℃[ppm] 0.18 <0.1 0.16 <0.1 0.1 0.11 Hysteresis@22℃[ppm] 0.27 0.14 0.24 0.14 0.16 0.17 Hysteresis@10℃[ppm] 0.61 0.42 0.54 0.38 0.85 0.43 Hysteresis@+5℃[ppm] 0.85 0.61 0.74 0.56 0.61 0.61 Hysteresis@0℃[ppm] 1.1 0.81 0.92 0.76 0.85 0.82 Hysteresis@-5℃[ppm] 1.2 0.96 1.16 0.93 1.04 0.97 Ceramic temperature[℃] Ceramicization duration [days] Average CTE (-30; +70℃) [ppm / K] Average CTE (-40; +80℃) [ppm / K] Table 2 (continued): Composition, ceramization and properties (Mol%)

[0238] Comparative Example No. (Comparative Example) 13 14 15 16 <![CDATA[Li 2 The]]> 8.4 8.2 9.4 9.3 <![CDATA[Na 2 The]]> 0.05 0.35 0.1 0.25 <![CDATA[K 2 The]]> 0.6 0.25 MgO 1.8 ZnO 0.95 1.2 0.60 CaO 2.3 2.35 1.0 BaO 0.85 SrO <![CDATA[Al 2 THE 3 ]]> 16.55 16.5 17 18.95 <![CDATA[SiO 2 ]]> 65.15 64.8 64.4 61.5 <![CDATA[P 2 THE 5 ]]> 3.4 3.3 3.5 4.05 <![CDATA[TiO 2 ]]> 2.0 2.0 1.95 2.05 <![CDATA[ZRO 2 ]]> 1.1 1.1 1.05 1.05 <![CDATA[As 2 THE 3 ]]> 0.15 0.2 0.2 0.15 sum 100.0 100.0 100.0 100.0 <![CDATA[SiO 2 +(5xLi 2 O)]]> MgO+ZnO 0.95 1.2 1.8 0.60 <![CDATA[ΣR 2 O(R=Na,K,Cs,Rb)]]> 0.05 0.35 0.7 0.50 ΣRO(R=Ca,Ba,Sr) 2.25 2.35 1.85 Va[℃] Ceramic temperature[℃] 770 810 790 830 Ceramicization duration [days] 5 1 5 2.5 Crystalline phase [Vol. %] 73 69 74 66 Crystal size [nm] 43 47 56 41 Average CTE (0; +50℃) [ppm / K] -0.03 -0.08 -0.06 0.07 TCL(0;+50℃) 4.29 |Expansion at 50°C| 3.55 Parameter F 1.21 Hysteresis@45℃[ppm] <0.1 <0.1 <0.1 <0.1 Hysteresis@35℃[ppm] <0.1 <0.1 <0.1 <0.1 Hysteresis@30℃[ppm] <0.1 <0.1 <0.1 <0.1 Hysteresis@22℃[ppm] 0.13 <0.1 0.16 <0.1 Hysteresis@10℃[ppm] 0.44 0.3 0.44 0.15 Hysteresis@+5℃[ppm] 0.67 0.55 0.63 0.23 Hysteresis@0℃[ppm] 0.97 0.84 0.85 0.35 Hysteresis@-5℃[ppm] 1.3 1.13 1.0 0.5 Ceramic temperature[℃] Ceramicization duration [days] Average CTE (-30; +70℃) [ppm / K] Average CTE (-40; +80℃) [ppm / K]

[0239] Table 3: Alternative parameter f T.i .Examples and comparative examples for selection

[0240] <![CDATA[f T.i. [ppm / K]]]> <![CDATA[Titanium-doped SiO 2 > Example 6 Example 7 Example 9 20-40℃ 0.024 0.004 0.0015 0.007 20-70℃ 0.039 0.0036 0.005 0.023 -10-30℃ 0.015 0.003 0.012 .

Claims

1. A LAS glass ceramic having a maximum value of 0±0.1×10 -6 / K and a thermal hysteresis of <0.1 ppm at least in the temperature range of 10-35 °C, and comprises the following components (in Mol % based on oxides): SiO2 60–71 Li2O 7–9.4 MgO+ZnO 0–<0.6 At least one component selected from the group consisting of P2O5, R2O, RO, wherein R2O may be Na2O and / or K2O and / or Cs2O and / or Rb2O, and RO may be CaO and / or BaO and / or SrO, A nucleating agent in an amount of 1.5 to 6 mol%, wherein: The nucleating agent is at least one component selected from the group consisting of TiO2, ZrO2, Ta2O5, Nb2O5, SnO2, MoO3, WO3, and HfO2, Among them, LAS glass ceramics contain up to 0.05 Mol% As2O3 as a fining agent.

2. LAS glass ceramics according to claim 1, wherein, It contains Al2O3 in an amount of 10 to 22 Mol%, preferably 11 to 21 Mol%, and / or P2O5 in an amount of 0.1 to 6 Mol%, preferably 0.3 to 5 Mol%.

3. LAS glass ceramics according to claim 1 or 2, wherein, The total content of ZnO+MgO is ≤0.55 Mol%, advantageously ≤0.5 Mol%, advantageously ≤0.45 Mol%, advantageously ≤0.4 Mol%, preferably ≤0.3 Mol%, preferably ≤0.2 Mol% and / or the content of MgO is ≤0.35 Mol%, preferably ≤0.3 Mol%, preferably ≤0.25, preferably ≤0.2 Mol%, more preferably ≤0.1 Mol% and / or the content of ZnO is ≤0.5 Mol%, preferably ≤0.45, preferably ≤0.4 Mol%≤0.3 Mol%, preferably ≤0.2 Mol%, more preferably ≤0.1 Mol%.

4. The LAS glass-ceramic according to any one of the preceding claims, wherein: The content of SiO2 is ≤70 Mol%, preferably ≤69 Mol%, particularly preferably ≤68.5 Mol%.

5. The LAS glass-ceramic according to any one of the preceding claims, wherein: The total content of RO (CaO+BaO+SrO) is ≥0.1 Mol%, preferably ≥0.2 Mol%, advantageously ≥0.3 Mol%, preferably ≥0.4 Mol% and / or ≤6 Mol%, preferably ≤5 Mol%, advantageously ≤4.5 Mol%, advantageously ≤4.0 Mol%, preferably ≤3.8 Mol%, preferably ≤3.5 Mol%, preferably ≤3.2 Mol%.

6. The LAS glass-ceramic according to any one of the preceding claims, wherein: The total content of RO2 (Na2O+K2O+Cs2O+Rb2O) is ≥0.1Mol%, preferably ≥0.2Mol%, advantageously ≥0.3Mol%, preferably ≥0.4Mol% and / or ≤6Mol%, advantageously ≤5Mol%, preferably ≤4Mol%, preferably ≤3Mol%, preferably ≤2.5Mol%.

7. The LAS glass-ceramic according to any one of the preceding claims, wherein the total content of the nucleating agent is ≥1.5 Mol%, preferably ≥2.5 Mol%, advantageously ≥3 Mol% and / or ≤6 Mol%, advantageously ≤5 Mol%, preferably ≤4.5 Mol%, preferably ≤4 Mol%.

8. The LAS glass-ceramic according to any one of the preceding claims, wherein: The conditions are suitable for: molar content SiO2+(5×molar content Li2O)≥106, preferably molar content SiO2+(5×molar content Li2O)≥107.5 and / or The conditions are suitable for: molar content SiO2+(5×molar content Li2O)≤115.5, preferably molar content SiO2+(5×molar content Li2O)≤114.

5.

9. The LAS glass-ceramic according to any one of the preceding claims, wherein: The processing temperature Va is at most 1330°C, preferably at most 1320°C.

10. The LAS glass-ceramic according to any one of the preceding claims, wherein: The main crystalline phase is high quartz mixed crystals and advantageously the average crystallite size of the high quartz mixed crystals is <100 nm, advantageously <80 nm, preferably <70 nm and / or the crystalline phase proportion is less than 70 vol%.

11. The LAS glass-ceramic according to any one of the preceding claims, wherein: Parameter F <1.2, preferably <1.1, preferably at most 1.05, where F = TCL (0; 50° C.) / | expansion (0; 50° C.) |.

12. The LAS glass-ceramic according to any one of the preceding claims, wherein: Substitution parameter f (20;40) <0.024ppm / K and / or alternative parameter f (20;70) <0.039ppm / K and / or alternative parameter f (-10;30) <0.015ppm / K.

13. The LAS glass-ceramic according to any one of the preceding claims, wherein: It has a relative length change (dl / l0) of ≤|0.10|ppm, preferably ≤|0.09|ppm, particularly preferably ≤|0.08|ppm, particularly preferably ≤|0.07|ppm in the temperature range of 20°C to 30°C and / or a relative length change (dl / l0) of ≤|0.17|ppm, preferably ≤|0.15|ppm, particularly preferably ≤|0.13|ppm, particularly preferably ≤|0.11|ppm in the temperature range of 20°C to 35°C.

14. The LAS glass-ceramic according to any one of the preceding claims, wherein: It has a relative length change (dl / l0) of ≤|0.30| ppm, preferably ≤|0.25| ppm, particularly preferably ≤|0.20| ppm, particularly preferably ≤|0.15| ppm in the temperature range from 20°C to 40°C.

15. The LAS glass-ceramic according to any one of the preceding claims, wherein: The CTE-T curve has a value of ≤0±2.5ppb / K in a temperature interval with a width of at least 30K. 2 , preferably ≤0±2ppb / K 2 , preferably ≤0±1.5ppb / K 2 , particularly preferably ≤0±1ppb / K 2 The slope of .

16. The LAS glass-ceramic according to any one of the preceding claims, wherein: It has a thermal hysteresis of <0.1 ppm at least in the temperature range of 5 to 45°C, advantageously at least in the temperature range of >0 to 45°C, preferably at least in the temperature range of -5 to 50°C.

17. The LAS glass-ceramic according to any one of the preceding claims, wherein: It contains ≤0.04 mol %, preferably ≤0.03 mol %, preferably ≤0.02 mol % As 2 O 3 , or particularly preferably is essentially free of As 2 O 3 .

18. The LAS glass-ceramic according to any one of the preceding claims, wherein: As a fining agent instead of As2O3 or in addition to up to 0.05 mol% As2O3, it has at least one alternative redox fining agent and / or at least one evaporative fining agent and / or at least one decomposition fining agent, Preferably, the alternative redox fining agent is selected from at least one component of the group consisting of Sb2O3, SnO2, MnO2, CeO2, Fe2O3 and / or the evaporative fining agent contains a halogen having a fining effect and / or the decomposition fining agent contains a sulfate component.

19. Use of the LAS glass-ceramic according to any of the preceding claims in precision components, in particular for use in metrology, spectroscopy, measurement technology, lithography, astronomy or Earth observation from space, for example as a mirror or mirror carrier for a segmented or integral astronomical telescope, or also as a reduced-weight or ultra-light mirror substrate, for example for a space-based telescope, or as a high-precision structural component for distance measurement, for example in space or in optics for Earth observation, as a precision component, for example a standard for precise measurement technology, a precision measuring rod, a reference plate in an interferometer, as a mechanical precision component, for example for a ring laser gyroscope, a helical spring for the watchmaking industry, for example as a mirror and prism in LCD lithography, and for example as a mask holder, wafer stage, reference plate, reference frame and grid plate in microlithography and EUV microlithography, and as a mirror and / or photomask substrate or photomask blank in EUV microlithography.